Methylparaben and ethylparaben exposure through breast milk in the first six months of lactation: A Taiwanese cohort study with estimated daily intake for breastfed infants - Ting Chang; Ching-Chung Tsai; Ting-I Lin; Hsien-Kuan Liu; Jau-Ling Suen; San-Nan Yang; Chien-Yi Wu; Pei-Ling Wu; Yung-Ning Yang (Food and Chemical Toxicology, 2026)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Modular memristor circuits for Pavlov associative memory with scalability - Xiaoyuan Wang; Zhenyu Ge; Mingyang Wu; Xinrui Zhang; Zhonghai Zhang; Xiaolu Lucia Li; Herbert Ho-Ching Iu; Sung-Mo Kang (Cognitive Neurodynamics, 2026)

Critical role of AaTgl1 lipase/hydrolase in virulence and lesion formation in Alternaria alternata - Jessalyn Marasigan Parco; Celine Yen Ling Choo; Hsin-Yu Lu; Pei-Ching Wu; Kuang-Ren Chung (Fungal Biology, 2026)

Metabolic and growth responses of rainbow trout (Oncorhynchus mykiss) to black soldier fly meal: A meta-analysis and multivariate evaluation of physiological trade-offs - KhaiHang Choong; ZeXin Li; Fui Fui Ching; Leong Seng Lim; Zhou Wu; Karsoon Tan (Aquaculture, 2026)

Subtropical climate and intraday temperature variability: Mental health risks and modifying roles of demographic and seasonal factors in Texas - Yue Zhang; Kaili Zhang; Yizhen Ding; Chia-Ching Wu; Dongying Li (Sustainable Cities and Society, 2026)

Electrochemically synthesized potassium ferrate for diclofenac degradation: Performance, kinetics, and mechanistic insights - Chia-Hung Chen; Ching-Lung Chen; Hsin-Yu Chiang; Wu-Xing Chen; Amila Kasun Abeysinghe; Fang-Yu Liang; Chih-Chi Yang; Yen-Ping Peng (Journal of Water Process Engineering, 2026)

Geosynthetic-reinforced soil check dam: Case study and numerical analyses - Hsin-Ming Wu; Kuo-Hsin Yang; Chen-Cheng Kao; Chaicharn Thongthanawat; Suched Likitlersuang; Jyun-Yen Wang; Feng-Chi Huang; Wei-Lung Huang; Ching-Shui Kuo (Geotextiles and Geomembranes, 2026)

Interfacial electron redistribution and tandem active sites enable enhanced nitrate to ammonia conversion in Zr-MOF/MoS2 heterostructures - Naveen Karuppusamy; Zi-Yan Zhan; Ruspika Sundaresan; Chun Hsien Wu; Pandiyarajan Anand; Jeyakumar Karthikeyan; Hsu-Feng Lee; Hung-Pin Hsu; Yu-Cheng Shao; Yi-Ping Wang; Ching-Wei Tung (Chemical Engineering Journal, 2026)

Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Altered dynamic functional connectivity of the language network associated with electronegative L5 in patients with mild cognitive impairment - Ping-Song Chou; Sharon Chia-Ju Chen; Mei-Chuan Chou; Chung-Yao Hsu; Meng-Ni Wu; Ching-Kuan Liu; Chiou-Lian Lai (GeroScience, 2026)

Real-world emission factors and inhalation health risks of PM-bound metals from workboats using ultra-low sulfur marine fuel - Po-Yen Chien; Chia-Hsiang Lai; Chia C. Wang; Dhruv Vishal Patel; Ajay Pillarisetti; Wu-Xing Chen; Chia-Hung Chen; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Dong-Ni Wu; I-Hsuan Wu; et al. (Environmental Pollution, 2026)

Chlorpyrifos exposure induced cytotoxic death in pancreatic islet β-cells via the functional co-activation of JNK and AMPKα signaling downstream-mediated mitochondria-dependent apoptosis pathway - Ching-Yao Yang; Kuan-I Lee; Ya-Wen Chen; Shing-Hwa Liu; Kai-Min Fang; Chun-Ying Kuo; Wei-Cheng Lia; Kai-Chih Chang; Jun-An Ke; Cheng-Tien Wu; Chun-Fa Huang; Chin-Chuan Su (Food and Chemical Toxicology, 2026)

Seismic performance and failure mechanisms of scaled reinforced concrete containment vessels under shake table testing - Chang-Ching Chang; Jiaji Wang; Chiun-lin Wu; Thomas T.C. Hsu; Kalyana B. Nakshatrala; Yi-Lung Mo (Engineering Structures, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

PM2.5 exposure and breast cancer risk: Independent and combined effects of ESR1 rs2046210 and FGFR2 rs2981582 in a Taiwanese cohort - Yi-Ching Liaw; Chih-Da Wu; Yi-Chia Liaw; Shu-Yi Hsu; Mu-Rong Chao; Chiung-Wen Hu; Yung-Po Liaw (Environmental Pollution, 2026)

Enabling fast Li+ transport and cycling stability in solid-state lithium metal batteries via fluorinated layered double hydroxide electrolyte fillers - John Peter Isaqu; Karuppiah Pandi; Yi-Shiuan Wu; Chun-Chen Yang; Ching-Yuan Su (Chemical Engineering Journal, 2026)

ICE1 plays a vital role in the development of pollen grains through regulating tapetum degradation and nutrient mobilization in Arabidopsis thaliana - Fa-Li Chang; Jer-Lun Kuo; Meng-Ting Wu; Ching-Hsing Liang; Shiang-Jiuun Chen; Chien-Chih Yang (Plant Molecular Biology, 2026)

From conceptual site models to data-driven insights: Key controls on vapor extraction performance in dual-phase extraction systems - Hsiao-Fen Wu; Shang-Lien Lo; Ching-Yao Hu; Pei-Te Chiueh (Journal of Environmental Management, 2026)

Development of a pomelo pectin–based microencapsulation system for Akkermansia muciniphila - Chang-Han Wang; Wen-Yu Liu; She-Ching Wu (Food Chemistry, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Insertion of the PgRE1 retrotransposon into the promoter region of PgACS1, a system-2 ACC synthase gene, leads to variation in ripening ethylene production and the storability of different guava varieties - Margo Sulistio; You-Siang Liao; Hsin-Hung Yeh; Ching-Ping Lin; Hung-Yeh Hsieh; Chun-Ta Wu (Postharvest Biology and Technology, 2026)

Effect of bed slope on turbidity currents interacting with an obstacle: Insights from Large Eddy Simulations - Said Alhaddad; Ching-Sen Wu; Lynyrd de Wit (Marine Geology, 2026)

Early-childhood exposure to per- and polyfluoroalkyl substances (PFAS) and neurobehavioral development in children - Chia-Jung Tung; Jia-Hwa Yang; Ching-Chun Lin; Chia-Yang Chen; Wu-Shiun Hsieh; Mei-Huei Chen; Pau-Chung Chen (Environmental Research, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Quasi-zero-stiffness bistable vibration energy harvester with self-decreasing potential barrier effect: Design, modeling, and experiments - Xianming Zeng; Ching-Tai Ng; Jiyang Fu; Nan Wu (Engineering Structures, 2026)

Anti-inflammatory constituents from Murraya paniculata var. omphalocarpa - Kun-Ching Cheng; Chia-Hung Wu; Hao-Ze Li; Tsong-Long Hwang; Ping-Chung Kuo; Tian-Shung Wu (Phytochemistry Letters, 2026)

Genomic epidemiology and antimicrobial resistance of nontyphoidal Salmonella in retail meats in Hong Kong: A comprehensive surveillance study using whole-genome sequencing - Ivan Tak-Fai Wong; Iain Chi-Fung Ng; Dorothy Hong-Ting Cheung; Wing-Yin Tam; Choi-Ying Wong; Sharon Ka-Yee Fung; Ho-Ching Tong; Shue-Kei Chan; Tsz-Ying Wu; Elaine Yin-Ting Yeung; Jiaying Zhang; Franklin Wang-Ngai Chow; et al. (Food Research International, 2026)

Atomic-scale CuOx–Fe3O4₋x/TiO2 heterostructures with defect synergy for highly selective and efficient reverse water–gas shift reaction - Po-Wen Cheng; Fa-Chih Pai; Chien-Yi Liu; Chih-Wei Hu; Ching-Yi Chou; Guo-Wei Lee; Chia-Shing Wu; Chun-Hong Kuo; Kuang-Kuo Wang; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Geochemical signatures of mud and core gases from the Milun Fault Scientific Drilling (MiDAS), Taiwan: Implications for fluid pathways and crustal degassing - Ching-Chou Fu; Kuo-Hang Chen; Kuo-Wei Wu; Pei-Ling Wang; Ai-Ti Chen; Vivek Walia; Kuo-Fong Ma (Chemical Geology, 2026)

Blood flow restriction modulates common drive to motor units and force precision: implications for neuromuscular coordination - Chia-Chan Wu; Yen-Ting Lin; Yueh Chen; Yi-Ching Chen; Ing-Shiou Hwang (European Journal of Applied Physiology, 2026)

Potential role of oocyte-intrinsic fatty acid synthesis in ovarian development of the bigfin reef squid Sepioteuthis lessoniana - Hau-Wen Li; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2026)
In most animals, excess dietary energy is stored as lipids in specialized tissues, such as the liver in vertebrates or the hepatopancreas and fat body in invertebrates, which function as energy reservoirs for reproduction. In cephalopods, however, dietary energy is rapidly mobilized from the digestive gland for growth rather than stored for reproduction. How excess energy is allocated for reproduction activity in cephalopods remains largely unclear. Lipogenesis is initiated by acetyl-CoA carboxylase (ACC), which converts acetyl-CoA derived from dietary carbon sources into malonyl-CoA; subsequent synthesis of saturated fatty acids is catalyzed by fatty acid synthase (FAS). Using the bigfin reef squid as a model, we investigate the role of fas in female development. fas mRNA was highly expressed in ovaries but weak in other tissues, including the lipid-rich digestive gland. fas showed female-biased expression in gonads, with level highest in juvenile ovaries and progressively decreasing to their lowest in mature ovaries. Expression was also high in primary and multiple follicular oocytes but declined in later stages. In situ hybridization and immunohistochemistry confirmed fas mRNA and protein localization in oocytes, particularly in primary and multiple follicular oocytes. In vitro ovarian culture further showed that inhibiting FAS activity enhanced somatic cell proliferation. Together, these findings suggest that squid ovary is a primary site of fatty acid synthesis, supporting early oocyte growth and membrane biogenesis in the absence of dedicated lipid storage tissues. The decline of FAS activity during oogenesis, and the associated reproduction in fatty acid synthesis, may act as a regulatory signal to promote somatic cell proliferation.

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Microplastics affect marine snow formation and sinking to the ocean's interior - Madeline Olivia; Wen-Huai Wu; An-Yi Tsai; Hung-Chu Hsu; Gwo-Ching Gong; Ruei-Feng Shiu (Water Research, 2026)

Closed-loop recovery of nickel sulfate hexahydrate from spent lithium-ion batteries for fabrication high-performances Ni-rich LiNi0.8Co0.1Mn0.1O2 cathode materials - Yola Bertilsya Hendri; Ching-Hsiang Hsu; Jia-Hao Hu; Yi-Shiuan Wu; Amun Amri; Chun-Chen Yang (Chemical Engineering Journal, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Emerging trends and clinical challenges in AI-enhanced emotion diagnosis using physiological data - Ying-Ying Tsai; Guan-Lin Wu; Yu-Jie Chen; Yen-Feng Lin; Ju-Yu Wu; Ching-Han Hsu; Lun-De Liao (Medical & Biological Engineering & Computing, 2026)

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Associations between parental shift work exposure and pregnancy outcomes: role of father’s shift work status - Chih-Fu Wei; Mei-Huei Chen; Ching-Chun Lin; Yueliang Leon Guo; Shio-Jean Lin; Ya-Wen Chen; Wu-Shiun Hsieh; Pau-Chung Chen (International Archives of Occupational and Environmental Health, 2025)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Social-ecological memories as references for biodiversity restoration and conservation action in coastal community - Chia-Hsuan Hsu; Yu-Wen Wu; Jiefeng Kang; Hung-Kai Chiu; Mei-Ching Li; Wei-Ting Chen (Marine Pollution Bulletin, 2025)

Unraveling urban plant diversity: The independent effects of plant species richness and greenness on health - Chia-Ching Wu; Chun-Yen Chang; Brian Deal; Dongying Li; William C. Sullivan (Urban Forestry & Urban Greening, 2025)

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Removal of oil/grease and anionic surfactants in carwash wastewater using an electrocoagulation-flotation (ECF) process: a pilot-scale study - Jung-Ming Wu; Wen-Hui Kuan; Li-Wei Ke; Ching-Yao Hu (Journal of Water Process Engineering, 2025)

Epigenetic transgenerational effects of prenatal exposure to 2,2′,4,4′-tetrabromodiphenyl ether on sperm function and DNA methylation in rat offspring - Ching-Shu Lai; Wei-Cheng Hsu; Jenq-Renn Chen; Bing-Mu Hsu; Kuo-Hsin Lee; Ping-Hsun Wu; Ping-Chi Hsu (Food and Chemical Toxicology, 2025)

Plasma-guided green synthesis of crystalline graphene quantum dots for broad-spectrum antiviral applications - Ren-Jie Weng; Li-Syuan Wu; Darwin Kurniawan; Ching-Tzu Chang; Ming-Han Tsai; Wei-Hung Chiang (Chemical Engineering Journal, 2025)

Natural lignan justicidin A-induced mitophagy as a targetable niche in bladder cancer - Kai-Hsun Chang; Hsin-Chih Chen; Ching-Ying Chen; Shu-Ping Tsai; Man-Yuan Hsu; Pao-Yuan Wang; Shan-Ying Wu; Chun-Li Su (Chemico-Biological Interactions, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Changes in Prooxidant and Antioxidant-Related Trace Element Levels During Helicobacter pylori Eradication Therapy - Ching-Chiang Lin; Ming-Kun Ku; Hsueh-Chiao Liu; Hui-Wen Chou; Po-Chih Chen; Deng-Chyang Wu; Yeou-Lih Huang (Biological Trace Element Research, 2025)

Long-term ecotoxicological effects of benzophenone-3 on the marine invertebrate, Crepidula onyx: Impacts on bioaccumulation, reproduction, shell integrity, condition indexes, and embryonic and larval development - Leyi Xi; Cheuk Fung Ng; Hei Ching Wong; Chris Kong Chu Wong; Rudolf Shiu Sun Wu; Yiu Fai Tsang; Vengatesen Thiyagarajan; Jill Man Ying Chiu (Journal of Hazardous Materials, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Segmentation of the Manila subduction zone and slab tearing beneath the Philippine mobile belt - Shu-Kun Hsu; Wen-Nan Wu; Lien-Kai Lin; Shiou-Ya Wang; Yi-Ching Yeh; Leo T. Armada; Carla B. Dimalanta; Kuan-Ting Chen; Yun-Jie Tsai; Ching-Hui Tsai (Journal of Asian Earth Sciences, 2025)

Molecular insights into the mechanism between the structural and mechanical properties of glycol chitosan methacrylate hydrogels - Kai-Hsiang Chang; Chia-Hung Wu; Zhen-Jie Gao; Yu-Chia Su; Ken-Tsung Wong; Yi-Cheun Yeh; Jiashing Yu; Chia-Ching Chou (Carbohydrate Polymers, 2025)

Community shift of aquatic insects following waste-water treatment implementation at Dongda Creek, Taichung City, Taiwan - Lilibeth A. Bucol; Ching-Chen Lee; Lan-Wai Yeh; Li-Wei Wu; Jyh-Min Chiang (Journal of Asia-Pacific Entomology, 2025)

Prenatal exposure to air pollution and pediatric acute leukemia: A nationwide study - Hsin-Chien Yen; I-Chieh Chen; Wei-Szu Lin; Kuan-Chia Lin; Meng-Che Wu; Ching-Heng Lin (Science of The Total Environment, 2025)

Utilizing natural compounds as ligands to disrupt the binding of SARS-CoV-2 receptor-binding domain to angiotensin-converting enzyme 2, impeding viral infection - Jingyi Wu; Ting-Hsu Chen; Zi-han Shen; May-Jywan Tsai; Max K. Leong; Yan-qiang Huang; Ching-Feng Weng (Phytochemistry Letters, 2025)

Enhanced removal of antimony, arsenic and cadmium by bone char in co-contaminated aqueous systems: A lattice level mechanistic understanding - Prakash C. Loni; Biqing Liang; Ching-Yu Chiang; Yao-Chang Lee; Jagat Rathod; Ci-Hong Ciou; Pei-Hua Wu; Wei-Hsin Chen (Journal of Environmental Chemical Engineering, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Polycyclic aromatic hydrocarbon-aryl hydrocarbon receptor signaling regulates chronic inflammation in lung-gut axis - Tzu-Yu Cheng; Ching-Shan Luo; Po-Hao Feng; Kuan-Yuan Chen; Chih-Cheng Chang; Nguyen Van Hiep; Yueh-His Chen; Yun-Kai Yeh; Sheng-Ming Wu (Toxicology and Applied Pharmacology, 2025)

The significance of the high-amplitude magnetic anomaly belt in the seismotectonics of mid-west Taiwan - Wen-Bin Doo; Yin-Sheng Huang; Wen-Nan Wu; Ching-Yu Cheng; Chung-Liang Lo; Hsueh-Fen Wang; Shiou-Ya Wang; Yin-Tung Yen (Journal of Asian Earth Sciences, 2025)

Tunable CO2 capture in N-ethylethylenediamine functionalized Mg2-MOF-74: unraveling the role of diamine basicity in reactivity and adsorption capacity - Santhanamoorthi Nachimuthu; Mao-Sheng Su; Liang-Ting Wu; Ching-Tsung Yu; Jyh-Chiang Jiang (Chemical Engineering Journal, 2025)

Fabrication of sesamin-loaded sodium caseinate nanoparticles: Insight to characterization, in vitro digestion, and molecular docking analysis - Wan-Yi Liu; Tzu-Yu Chen; Yun-Shan Hsieh; Yung-Yi Cheng; Shiou-Ling Li; Li-Ching Chang; Yu-Tse Wu (Food Bioscience, 2025)

Bio-active metabolites from Chinese Medicinal Herbs for treatment of skin diseases - Xiao Xiao Wu; Siu Kan Law; Hui Ma; Zhou Jiang; Yi Fan Li; Dawn Ching Tung Au; Chun Kwok Wong; Di Xian Luo (Natural Product Research, 2025)

Occurrence & characterization of Staphylococcus aureus from ready-to-eat (RTE), and cooked food in Singapore: A retrospective analysis - Ye Htut Zwe; Roshini Devi Mohan; Si Jia Lim; Wai Ching Lai; Kae Hwan Sim; Yu Lee Leyau; Ker Lew; Joachim Mun Choy Chua; Kyaw Thu Aung; Kern Rei Chng; Yuan Sheng Wu; Joanne Sheot Harn Chan; et al. (International Journal of Food Microbiology, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Blood and cloacal microbiome profile of captive green turtles (Chelonia mydas) and hawksbill turtles (Eretmochelys imbricata): Water quality and conservation implications - Xin Li Ching; Syamsyahidah Samsol; Mohd Uzair Rusli; Mohamad Aqmal-Naser; Joseph Anak Bidai; Christian Sonne; Xin Wu; Nyuk Ling Ma (Chemosphere, 2025)

Knockout of dead end 1 by CRISPR/Cas9 leads to loss of germ cells and male-biased sex development in freshwater angelfish (Pterophyllum scalare) - Wai-Kwan Chu; Shih-Chin Huang; Ching-Fong Chang; Yu-Ho Lin; Jen-Leih Wu; Hong-Yi Gong (Aquaculture, 2025)

Dynamic vertical land motion driven by climate and humans in the metropolitan Taipei Basin - Pei-Chin Wu; Meng (Matt) Wei; Jyr-Ching Hu; Steven D'Hondt; Hsin Tung; Shao-Hung Lin; Christopher J. Russoniello (Remote Sensing Applications: Society and Environment, 2025)

Junceellolide Q, a new polyacetoxybriarane from the delicate sea whip octocoral Junceella fragilis - Yih-Gang Goan; Mingzi M. Zhang; Lun Kelvin Tsou; Zhi-Hong Wen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yu-Jen Wu; Jih-Jung Chen; Hai Nhat Do; Pei-Luen Jiang; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Boosting anode interfacial stability in All-Solid-State lithium hybrid batteries with MCMB-Modified stainless steel current collector - Abebe Taye Fenta; Yosef Nikodimos; Semaw Kebede Merso; Ayenew Meniber; Misganaw Adigo Weret; Kassie Nigus Shitaw; Bereket Woldegbreal Taklu; Felika Valencia; Tsung-I Yeh; Chia Lung Hsieh; Chia-Yu Chang; Ya-Jun Liu; et al. (Chemical Engineering Journal, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Possible role of autophagy in microbial volatile pollutant-induced starch degradation and expression of hypoxia responsive genes - Chung-Chih Huang; Ching-Han Chang; Tu-Trinh Thi Truong; Wu-Guei Wang; Che-Hui Lin; Chih-Yun Chiang; Iwai Obayashi; Hao-Jen Huang (Environmental Pollution, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Nonlinear finite element model updating and fourier neural operator for digital twin of reinforced concrete containment vessel under seismic excitations - Si Fu; Chang-Ching Chang; Chawit Kaewnuratchadasorn; Jiaji Wang; Chiun-Lin Wu; Yi-Lung Mo; Thomas T.C. Hsu (Engineering Structures, 2025)

Evaluation of wind-induced response of high-rise structure with TMD system by real-time hybrid simulation test with motor-driven shaking table - JiaLei Wang; JiYang Fu; JiuRong Wu; YanHui Liu; HuiMeng Zhou; Ching Tai Ng; QiongXiang Liu (Engineering Structures, 2025)

Enhancing cisplatin efficacy in hepatocellular carcinoma with selenocystine: The suppression of DNA repair and inhibition of proliferation in hepatoma cells - Pei-Yi Wu; Ulfah Hasanah; Sheng-Hua Yang; Sin-Yi Chen; Yueh-Hsia Luo; Chien-Chin Chen; Ssu-Ching Chen (Chemico-Biological Interactions, 2025)

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

A ratiometric turn-on chemosensor for highly selective and sensitive visual detection of Zn2+ and its applications to environmental samples - Keerthika Kumarasamy; Zhe-Wei Wu; Wei-Jyun Chien; Mei-Ching Lin; Selva Kumar Ramasamy (Journal of Environmental Chemical Engineering, 2024)

Exploring the link between metformin use and adhesive capsulitis of the shoulder: a retrospective cohort study in Taiwan - Bing-Sian Lin; Wu-Chien Chien; Chieh-Hua Lu; Chi-Hsiang Chung; Chang-Huei Tsao; Tzu-Hsuan Weng; Ching-Yueh Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Maintaining KEAP1 levels in retinal pigment epithelial cells preserves their viability during prolonged exposure to artificial blue light - Ching-Hao Li; Tsung-Min Yang; Ida Fitriana; Te-Chao Fang; Liang-Huan Wu; George Hsiao; Yu-Wen Cheng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Development of fermented Atemoya (Annona cherimola × Annona squamosa)-Amazake increased intestinal next-generation probiotics - Yeu-Ching Shi; She-Ching Wu; Yi-Ching Lin; Yu-Juan Zheng; Cheng-Hao Huang; Bao-Hong Lee (Food Chemistry, 2024)

Exploring building vibration dynamics in the wake of the Chi-Chi earthquake: implications for natural hazard preparedness - David Ching-Fang Shih; Yih-Min Wu (Natural Hazards, 2024)

Wave-inspired piezoelectric bistable energy harvester considering stress distribution: Design, simulation and experimental investigation - Chao Xiong; Nan Wu; Jiyang Fu; Ching-Tai Ng; Jiurong Wu; Yuncheng He; Xianming Zeng (Engineering Structures, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Correction: Potential Factors Associated with the Blood Metal Concentrations of Reproductive-Age Women in Taiwan - Tsung-Ho Ying; Chun-Jui Huang; Chia-Jung Hsieh; Pei-Ju Wu; Chang-Ching Yeh; Ping-Kun Hung; Wei-Hsiang Chang; Meng-Hsing Wu; Hsin Hung; Jung-Wei Chang; Chen-Tai Wang; Rachelle D. Arcega; et al. (Exposure and Health, 2024)

Phylogenetic placements and phenotypic traits of soft rot bacteria isolated from potato (Solanum tuberosum) in Taiwan - Liang-Hsuan Wang; Wen-Chien Tang; Reun-Ping Goh; Jiun-Jie Chan; Yen-Hsin Chiu; Yea-Fang Wu; Shih-Min Su; Dao-Yuan Xue; Chia-Ching Chu (Journal of Plant Pathology, 2024)

The Impact of Coal-Fired, Soot on China's Industrial Production and Total Factor Energy Efficiency - Zhihuan Xu; Taisheng Zhang; Lei Zhuang; Po-Feng Wu; Ching-Cheng Lu (Water, Air, & Soil Pollution, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Surface ligand engineering of perovskite quantum dots for n-type and stretchable photosynaptic transistor with an ultralow energy consumption - Wei-Cheng Chen; Yan-Cheng Lin; Zih-Syuan Syu; Ya-Shuan Wu; Kai-Wei Lin; Cheng-Liang Liu; Chi-Ching Kuo; Wen-Chang Chen (Chemical Engineering Journal, 2024)

Enhancing dye degradation in darkness: The role of SnO2 nanorod clusters in flexocatalysis - Nai-Jen Chang; Yu-Ching Chen; Sz-Nian Lai; Jyh Ming Wu (Chemical Engineering Journal, 2024)

Marine anticancer drugs in modulating miRNAs and antioxidant signaling - Ya-Ting Chuang; Ching-Yu Yen; Jen-Yang Tang; Kuo-Chuan Wu; Fang-Rong Chang; Yi-Hong Tsai; Tsu-Ming Chien; Hsueh-Wei Chang (Chemico-Biological Interactions, 2024)

Low C4A copy numbers and higher HERV gene insertion contributes to increased risk of SLE, with absence of association with disease phenotype and disease activity - Christina Mary Mariaselvam; Gaurav Seth; Chengappa Kavadichanda; Wahid Boukouaci; Ching-Lien Wu; Bruno Costes; Molly Mary Thabah; Rajagopal Krishnamoorthy; Marion Leboyer; Vir Singh Negi; Ryad Tamouza (Immunologic Research, 2024)

Water-energy-food(WEF) nexus efficiency of dynamic slack-based measure in 31 provinces and regions in China - Yunyun Gao; Ching-Cheng Lu; Wan-Shui Wu (Journal of Cleaner Production, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Enhancing methane formation in carbon dioxide hydrogenation on nickel clusters with zirconium additives: Exploring active sites, reaction pathways, and catalytic mechanisms - Ching-Shiun Chen; Tse-Ching Chen; Jia Huang Wu; Hung-Chi Wu; Chia-Min Yang; Tsung-Cheng Yang; Chih-Wen Pao (Chemical Engineering Journal, 2024)

Multiscale Variability of Autumn Precipitation in Eastern Taiwan Modulated by ENSO, ISO, and TC Activity - Ching-Hsuan Wu; Wei-Ting Chen; Chien-Ming Wu (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Longitudinal assessment of oxidative stress markers and their relationship with exposure to PM2.5 and its bound metals in healthy participants - Yuan-Ting Hsu; Ting-Yao Su; Trong-Neng Wu; Wei-Te Wu; Saou-Hsing Liou; Ching-Huang Lai; Shau-Ku Huang (International Journal of Hygiene and Environmental Health, 2024)

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

Meteotsunamis in the Tamsui River estuary, Taiwan - Li-Ching Lin; Wen-Cheng Liu; Chin H. Wu (Estuarine, Coastal and Shelf Science, 2024)

Correction: Potential Factors Associated with the Blood Metal Concentrations of Reproductive-Age Women in Taiwan - Tsung-Ho Ying; Chun-Jui Huang; Chia-Jung Hsieh; Pei-Ju Wu; Chang-Ching Yeh; Ping-Kun Hung; Wei-Hsiang Chang; Meng-Hsing Wu; Hsin Hung; Jung-Wei Chang; Chen-Tai Wang; Rachelle D. Arcega; et al. (Exposure and Health, 2024)

The synergistic effect of insomnia and depression on risk of herpes zoster - Hsueh-Ching Wu; Chia-Ling Lin; Chi-Hsiang Chung; Wu-Chien Chien (Journal of NeuroVirology, 2024)

Longitudinal aortic strain, ventriculo-arterial coupling and fatty acid oxidation: novel insights into human cardiovascular aging - Hongzhou Zhang; Shuang Leng; Fei Gao; Jean-Paul Kovalik; Ru-San Tan; Hai Ning Wee; Kee Voon Chua; Jianhong Ching; Xiaodan Zhao; John Allen; Qinghua Wu; Tim Leiner; et al. (GeroScience, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Population genetic diversity and structure of the Taiwan endemic cyprinid fish Candidia barbata (Cyprinidae): human intervention - Yu-Min Ju; Jui-Hsien Wu; Po-Hsun Kuo; Kui-Ching Hsu (Hydrobiologia, 2024)

Different microbial communities in paddy soils under organic and nonorganic farming - Jimmy Kuo; Daniel Liu; Wei Hao Wen; Ching Yuan Chiu; Wanyu Chen; Yun Wen Wu; Fang-Ting Lai; Chorng-Horng Lin (Brazilian Journal of Microbiology, 2024)

Macular pigments produced from microalga Chlorella sp. and applied to alleviate the pathogenic process in diabetic mice - Meng-Wei Lin; Wei-Hong Chiu; Cheng-Han Lin; Dung-Huan Liu; Pei-Ching Wu; Chih-Sheng Lin (Algal Research, 2024)

Exposure estimates of PM2.5 using the land-use regression with machine learning and microenvironmental exposure models for elders: Validation and comparison - Chin-Yu Hsu; Wei-Ting Hsu; Ching-Yi Mou; Pei-Yi Wong; Chih-Da Wu; Yu-Cheng Chen (Atmospheric Environment, 2024)

Landscape naturalness and restoring benefit: a connection through bird diversity - Joanne Chang; Chia-Ching Wu; Chun-Yen Chang (Urban Ecosystems, 2024)

Potential Factors Associated with the Blood Metal Concentrations of Reproductive-Age Women in Taiwan - Tsung-Ho Ying; Chun-Jui Huang; Chia-Jung Hsieh; Pei-Ju Wu; Chang-Ching Yeh; Ping-Kun Hung; Wei-Hsiang Chang; Meng-Hsing Wu; Hsin Hung; Jung-Wei Chang; Chen-Tai Wang; Rachelle D. Arcega; et al. (Exposure and Health, 2024)
Exposure of reproductive-age women to toxic trace elements warrants attention because of their negative effects. This study aimed to investigate the levels of arsenic (As), cadmium (Cd), mercury (Hg), chromium (Cr), and lead (Pb) in the blood of 837 Taiwanese childbearing-age women and establish the correlation between their dietary pattern and heavy metal concentration. The concentrations of Cd and Pb were significantly higher in nonpregnant women than in pregnant women (Cd: 2.41 µg/L vs. 2.12 µg/L; Pb: 0.83 µg/dL vs. 0.73 µg/dL), whereas the concentration of Cr was significantly lower in nonpregnant women than in pregnant women (Cr: 0.98 µg/L vs. 1.05 µg/L). Otherwise, no significant differences in As (9.02 µg/L vs. 9.51 µg/L) and Hg (3.71 µg/L vs. 3.79 µg/L) were found between the nonpregnant and pregnant women. Overall, the blood metal concentrations of Cd and Hg showed a decreasing trend in the different pregnancy stages. The levels of As and Hg were highly correlated with seafood intake. Finally, lifestyle habits, such as burning incense usage and Chinese herb intake may contribute to metal accumulation in maternal or reproductive-age women. Preventive risk communication and educational strategies should be applied to these subgroups in view of food safety and public health concern. Graphical Abstract

A 16-year meteotsunami climatology in the coastal areas of southern Asia-Pacific Ocean - Li-Ching Lin; Wen-Cheng Liu; Chin H. Wu (Frontiers in Marine Science, 2024)
This study presents the meteotsunami behavior in response to different storm types in the coasts of southern Asia-Pacific Ocean from 16 years water level records. Through the size- frequency analysis, the dangerous meteotsunami, wave height exceeding 0.3 m, can occur up to 44 events per year. Notably, during the extreme waves of the 2007 event, wave heights reached approximately 0.9-1.5 m in the Taiwan Strait and the western coastal areas of Taiwan. We have classified storms into six types by radar reflectivity images and satellite-derived precipitation. Findings indicate that predicted wave heights caused by bows and typhoons could reach hazardous magnitude of exceeding 2 m in a 100-yr interval. Spatial and temporal analysis reveals that meteotsunami occurrences are most frequent in the western regions during the winter to early spring months (December to April). Of all meteotsunami occurrences, cluster storms are identified as the most prevalent atmospheric forcing, accounting for 60% of meteostunamis. Typhoons have a 20% association with meteotsunamis along the east coasts of Taiwan during late summer to autumn. On the east coasts, typhoon type-induced events may be attributed to the combination effect of meteotsunamis and infra-gravity waves. Overall, this study provides the first comprehensive examination of meteotsunami-storm characteristics and their associated hazard risks in the coastal areas of the southern Asia-Pacific Ocean.

Consumption of the nonnutritive sweetener acesulfame potassium increases central precocious puberty risk - Hung-Tsung Wu; Chi-Chen Chiang; Chung-Teng Wang; Yue-Hwa Chen; Shih-Yuan Hsu; Yang-Ching Chen (Journal of Hazardous Materials, 2024)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Effect of sodium promoters on Ni/Al2O3 catalyst for CO2 hydrogenation: The carbon fixation as carbon nanofiber and reverse-water gas reactions - Ching-Shiun Chen; Tse-Ching Chen; Hung-Chi Wu; Jia-Huang Wu; Chih-Wen Pao (Chemical Engineering Journal, 2023)

Generation of artificial rainfall events for flood risk assessment in Taiwan - Wen-Ko Hsu; Pei-Chiung Huang; Ching-Cheng Chang; Wei-Ling Chiang; Dung-Jiang Chiou; Cheng-Wu Chen (Natural Hazards, 2023)

Pinostrobin modulates FOXO3 expression, nuclear localization, and exerts antileukemic effects in AML cells and zebrafish xenografts - Pei-Yi Chen; Ching-Yen Lin; Chia-Ling Wu; Pei Ying Keak; Je-Wen Liou; Wan-Yun Gao; Liang-In Lin; Jui-Hung Yen (Chemico-Biological Interactions, 2023)

Overexpression of OsHsp 18.0 in rice enhanced tolerance to heavy metal stress - Tong-Seung Tseng; Senthil Kumar Rajendran; Yi-Hsin Liu; Shaw-Jye Wu; Chung-An Lu; Ching-Hui Yeh (Plant Cell Reports, 2023)

Interaction between driftwood deposition patterns and debris flow fan development - Yen-Yu Chiu; Jia-Yen Wu; Hung-En Chen; Ching-Ying Tsou; Su-Chin Chen (Landslides, 2023)

Utilizing Numerical Models and GIS to Enhance Information Management for Oil Spill Emergency Response and Resource Allocation in the Taiwan Waters - Chi-Min Chiu; Laurence Zsu-Hsin Chuang; Wei-Liang Chuang; Li-Chung Wu; Ching-Jer Huang; Yinglong Joseph Zhang (Journal of Marine Science and Engineering, 2023)
This study aims to establish a comprehensive workflow for developing emergency response plans for both actual and scenario oil spill incidents in the Taiwan waters while addressing the resource allocation for oil spill containment as well. This workflow comprises two vital components. The first component involves the integration of numerical tools and observational data, which includes the incorporation of wind data from sources such as the National Centers for Environmental Prediction (NCEP) or meteorological stations. Additionally, it incorporates ocean current data simulated by the semi-implicit cross-scale hydroscience integrated system model (SCHISM) into the general NOAA operational modeling environment (GNOME) model, which is a new approach for this purpose. In order to assess the efficacy of this component, two distinct case studies were conducted. The first case study focused on an incident in a northern coastal area of Taiwan under open sea conditions, whereas the second case study examined an incident within a major commercial harbor in central Taiwan. The second component of this workflow involves creating oil risk maps by integrating the results from the first component with specific geographical factors into Google Earth. These oil risk maps serve multiple purposes. They offer real-time information to emergency response commanders regarding oil spill hazard prediction, and they also enable the effective development of emergency response strategies and disposal plans for potential oil spill incidents. This is achieved by generating risk maps for various scenarios using the approach outlined in the first component. Additionally, these maps assist in the assessment and planning of resource allocation for oil containment.

Microplastics in the soil environment: Focusing on the sources, its transformation and change in morphology - Junyu Zhu; Guowen Dong; Fu Feng; Jing Ye; Ching-Hua Liao; Chih-Hung Wu; Sheng-Chung Chen (Science of The Total Environment, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

A concise chemoenzymatic total synthesis of neutral Globo-series glycosphingolipids Globo A and Globo B, and Forssman and para-Forssman antigens - Yu-Ching Chiang; Chun-Yen Wu; Pei-Yun Chiang; Avijit K. Adak; Chun-Cheng Lin (Glycoconjugate Journal, 2023)

First report of lisianthus wilt caused by Fusarium oxysporum f. sp. eustomae in Taiwan - Cheng-Chun Wu; Yuan-Min Shen; Ya-Ching Teng; Wen-Hsin Chung (Crop Protection, 2023)

Duplicated paralog of sulfide: quinone oxidoreductase contributes to the adaptation to hydrogen sulfide-rich environment in the hydrothermal vent crab, Xenograpsus testudinatus - Chi Chen; Guan-Chung Wu; Yao-Tse Chung; Hau-Wen Li; Pei-Hsuan Chou; Yung-Che Tseng; Chieh-Jhen Chen; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2023)

A mass-preserving level set method for simulating 2D/3D fluid flows with deformed interface - Hao-Liang Wen; Ching-Hao Yu; Tony Wen-Hann Sheu; Shiu-Wu Chau (Ocean Engineering, 2023)

Automatic modal identification via eigensystem realization algorithm with improved stabilization diagram technique - Wen-Hai Feng; Chao-Yuan Wu; Ji-Yang Fu; Ching-Tai Ng; Yun-Cheng He (Engineering Structures, 2023)

Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Yan-Ding Lin; Pei-Wan Hsiao; Wun-Yu Chen; Sih-Yu Wu; Wei-Min Zhang; Chin-Wei Lu; Hai-Ching Su (Chemical Engineering Journal, 2023)

Livistona chinensis Water Extract has the Potential to Repair Thioacetamide-Induced Liver Fibrosis in Mice - San-Ho Hung; Tzu-Hsuan Hsu; Chun-Shien Wu; Yi-Ping Lin; Ching-Ting Wei; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Predicting survival after radiosurgery in patients with lung cancer brain metastases using deep learning of radiomics and EGFR status - Chien-Yi Liao; Cheng-Chia Lee; Huai-Che Yang; Ching-Jen Chen; Wen-Yuh Chung; Hsiu-Mei Wu; Wan-Yuo Guo; Ren-Shyan Liu; Chia-Feng Lu (Physical and Engineering Sciences in Medicine, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Effects of prebiotics on intestinal physiology, neuropsychological function, and exercise capacity of mice with sleep deprivation - Yi Chung; Jia-Ling Wu; Wen-Ching Huang (Food Research International, 2023)

Nitrogen-phosphorous co-doped palladium electrocatalyst for glycerol electro-oxidation reaction (GEOR): An efficient system for mesoxalic acid and dihydroxyacetone production - Muhammad Sheraz Ahmad; Kim Hoong Ng; Ching-Lung Chen; Faryal Kabir; Thongthai Witoon; Ta Yeong Wu; Chin Kui Cheng (Fuel, 2023)

In situ derived sulfated/sulfonated carbon nanogels with multi-protective effects against influenza a virus - Hung-Yun Lin; Ka-Long Luo; Ju-Yi Mao; Chin-Jung Lin; Chen-Yow Wang; Lauren Panny; Shiow-Yi Chen; Shih-Chao Lin; Chih-Ching Huang; Scott G. Harroun; Robert Y.L. Wang; Chang-Jer Wu (Chemical Engineering Journal, 2023)

Transcriptomic profile of symbiotic accessory nidamental gland during female maturation in bigfin reef squid - Peng-Wei Tseng; Hau-Wen Li; Chih Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2023)
The bigfin reef squid, Sepioteuthis lessoniana , are a valuable commercial species in East Asian regions such as Taiwan and Japan. A lack of genomic information limits the application of potential aquaculture techniques, especially in breeding when considering the hatching rate of offspring. In some squids and cuttlefishes, symbiotic bacteria are transmitted from the accessory nidamental gland (ANG) to the jelly coat of eggs. In Hawaiian bobtail squid, these parent-delivered mutualistic bacteria play an important role in preventing lethal biofouling of the eggs and accelerating the hatch rate of offspring. The bacterial consortium, which is housed in the female squids ANG, are governed by host selection during female maturation. Immune functions are typically used to explain the regulatory mechanism of symbioses by host selection. In this study, we evaluated the transcripts featured in bacterial selection and maintenance during ANG development using RNA-seq. Different developmental stages of ANGs (stages 1–4) were sequenced. The de novo transcriptome assembly resulted in 524,918 unigenes. Two groups, non-pigmentation group (stage 1 and stage 3) and pigmentation group (stage 4), were clustered by transcriptome-wide expression profile analysis. The gene expression analyses indicated that 9,475 differential expression genes (DEGs) in three different phases and 1,363 (14.3%) DEGs were matched in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Furthermore, KEGG-enriched analysis results suggested that immune responses are a dominant pathway in the non-pigmentation group (stage 1 and stage 3) whereas lipid metabolism and metabolism of flora fermentation are dominant in the pigmentation group (stage 4). Although the host immunity plays an important role during bacterial colonization of the ANG in bigfin reef squid, our results showed that most immune-related genes had a reduced transcriptomic level in the pigmentation group compared with the non-pigmentation group. Therefore, our results provide new insight to understand the regulatory mechanisms of initial bacterial colonization and later bacterial pigmentation in the bigfin reef squid.

Two new chromones and a new coumarin from the fruit of Cnidium monnieri (L.) Cusson - Hui-Chi Huang; Chun-Hsiang Lin; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Che-Yi Chao; Guan-Jhong Huang; Yueh-Hsiung Kuo (Natural Product Research, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Removal of tetracycline by a photocatalytic membrane reactor with MIL-53(Fe)/PVDF mixed-matrix membrane - Chien-Jung Wu; Irish Valerie Maggay; Ching-Hsueh Chiang; Wei Chen; Yung Chang; Chechia Hu; Antoine Venault (Chemical Engineering Journal, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

The involvement of AtMKK1 and AtMKK3 in plant-deleterious microbial volatile compounds-induced defense responses - Ching-Han Chang; Wu-Guei Wang; Pei-Yu Su; Yu-Shuo Chen; Tri-Phuong Nguyen; Jian Xu; Masaru Ohme-Takagi; Tetsuro Mimura; Ping-Fu Hou; Hao-Jen Huang (Plant Molecular Biology, 2023)

Durations of virtual exposure to built and natural landscapes impact self-reported stress recovery: evidence from three countries - Pongsakorn Suppakittpaisarn; Chia-Ching Wu; Yu-Hsin Tung; Yu-chen Yeh; Chulalux Wanitchayapaisit; Matthew H. E. M. Browning; Chun-Yen Chang; William C. Sullivan (Landscape and Ecological Engineering, 2023)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

Pharmaceutical nanoformulation strategies to spatiotemporally manipulate oxidative stress for improving cancer therapies — exemplified by polyunsaturated fatty acids and other ROS-modulating agents - Rui Xue Zhang; Franky Fuh-Ching Liu; Hoyin Lip; Junhong Liu; Qianrong Zhang; Xiao Yu Wu (Drug Delivery and Translational Research, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

The Characteristics and Expression Profile of Peptidoglycan Recognition Protein 2 in the Accessory Nidamental Gland of the Bigfin Reef Squid During Bacterial Colonization - Hau-Wen Li; Wei-Lun Kuo; Chi Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2022)
Some cephalopods carry microorganisms in two specialized organs, the light organ and the accessory nidamental gland (ANG). For the light organ, comprehensive mechanisms have been described for winnowing (bacterial selection) and maintenance of the symbiotic luminescent bacterium Vibrio fischeri ( V. fischeri ). However, the mechanisms controlling bacterial selection and maintenance during bacterial colonization of the ANG are open biological issues with physiological significance. Our recent study on bigfin reef squid ( Sepioteuthis lessoniana ) already showed that the ANG bacterial community shifts gradually and exhibits decreased diversity throughout maturation. This study further describes a potential role of an innate immunity-involved molecule, peptidoglycan recognition proteins (PGRPs), in the ANG of bigfin reef squid during bacterial transmission and colonization. First, we found that four homologs of the PGRP family are expressed in the ANG of bigfin reef squid ( sl PGRP2-5), but only slPgrp2 transcript levels are highly correlated with ANG development and bacterial colonization. Besides, slPgrp2 transcripts are mainly expressed in the epithelial cells of certain secondary tubules of ANG, and the expression levels are varied in the epithelial cells of other secondary tubules. This data reveals that slPgrp2 transcripts may associate with the composition of bacterial consortium and its secretary factors. Moreover, recombinant sl PGRP2 had a negative effect of Escherichia coli ( E.coli ) which inhibited bacterial growth in culture. Therefore, our data suggest slPgrp2 expression in the epithelial cells of secondary tubules in the ANG may have an essential role in the winnowing and maintenance of holobiont homeostasis in bigfin reef squid.

Interleukin-6 transiently promotes proliferation of osteoclast precursors and stimulates the production of inflammatory mediators - Peng-Yuan Chang; Hung-Kang Wu; Yu-Hsu Chen; Yu-Pao Hsu; Ming-Te Cheng; Ching-Hsiao Yu; Shau-Kwaun Chen (Molecular Biology Reports, 2022)

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Potential Effect of the Intrusion of the Kuroshio Current into the South China Sea on Catches of Japanese Eel (Anguilla Japonica) in the South China Sea and Taiwan Strait - Ching-Hsien Ho; Long-Jing Wu; Zhen Lu; Bo-Yi Lu; Yang-Chi Lan (Journal of Marine Science and Engineering, 2021)
This study examined the effect of the intrusion of the Kuroshio Current (KC) into the South China Sea (SCS) and the Taiwan Strait (TS) (SCS–TS region) on changes in catches of larval A. japonica in the traditional fishing ground waters of Gaoping near southwestern Taiwan in the SCS–TS region. First, the oceanic environment and recruitment trends from 1967 to 2019 were investigated based on secondary data. Then, field surveys were conducted to obtain primary data regarding the intrusion of the KC into the SCS, as well as the changes in the fishing sites and catches of A. japonica in the fall and winter of 2014–2015. Hence, the association between oceanic conditions and the number of A. japonica migrating into the SCS–TS region was explored. From 1967 to 2019, the recruitment proportion in the fishing grounds that formed due to the Kuroshio Branch Current (PKSBC) fluctuated significantly. Overall, positive values were observed for the Oceanic Niño Index for each year with a PKSBC > 50%, corresponding to El Niño conditions. In each year with a PKSBC > 70%, a looping path and a warm–core eddy appeared.

Optimizing the Design of Blood–Brain Barrier-Penetrating Polymer-Lipid-Hybrid Nanoparticles for Delivering Anticancer Drugs to Glioblastoma - Taksim Ahmed; Fuh-Ching Franky Liu; Chungsheng He; Azhar Z. Abbasi; Ping Cai; Andrew M. Rauth; Jeffery T. Henderson; Xiao Yu Wu (Pharmaceutical Research, 2021)

Streptococcus vaginalis sp. nov., a novel bacterial species isolated from vaginal swabs of a pregnant woman with diabetes - An-Shine Chao; Chiao-Yun Lin; Angel Chao; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Yi-Sheng Chen (Archives of Microbiology, 2021)

Biogas Production and Microbial Communities in the Anaerobic Digestion of Sewage Sludge Under Hydrothermal Pretreatment with Air and a Catalyst - Van Toi Pham; Pei-Hsun Wu; Chung-Yu Guan; Chia-Chi Chang; Bo-Liang Liu; Ching-Yuan Chang; Chang-Ping Yu (BioEnergy Research, 2021)

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

A real-time camera-based adaptive breathing monitoring system - Yu-Ching Lee; Abdan Syakura; Muhammad Adil Khalil; Ching-Ho Wu; Yi-Fang Ding; Ching-Wei Wang (Medical & Biological Engineering & Computing, 2021)

Effect of selected sampling media, flow rate, and time on the sampling efficiency of a liquid impinger packed with glass beads for the collection of airborne viruses - Yen-Chi Chen; I-Jen Wang; Chih-Ching Cheng; Yu-Chiao Wu; Chun-Hsuan Bai; Kuo-Pin Yu (Aerobiologia, 2021)

Community Assembly Processes as a Mechanistic Explanation of the Predator-Prey Diversity Relationship in Marine Microbes - Feng-Hsun Chang; Jinny Wu Yang; Ariana Chih-Hsien Liu; Hsiao-Pei Lu; Gwo-Ching Gong; Fuh-Kwo Shiah; Chih-hao Hsieh (Frontiers in Marine Science, 2021)
Predator and prey α-diversities are often positively associated; yet, understandings of the underlying mechanisms require manipulative experiments and thus remain unclear. We attempt to address this issue by deciphering how α-diversity of predator and prey influences each other’s community assembly processes, which subsequently determine their α -diversity. The occurrence of assembly processes was indicated by the mean pairwise taxonomic index within a community ( αMPTI ), assuming assembly processes left traceable imprints on species’ phylogeny. Specifically, αMPTI quantifies deviations of observed phylogenetic distances from that of random, so that it can be used to hint at the occurrence of non-random/deterministic assembly processes. Larger αMPTI of a community implies the occurrence of weaker homogenizing deterministic assembly processes, which suggests that this community might be comprised of less similar species and thus has higher α-diversity. We hypothesize that higher predator and prey α-diversity would be positively associated with each other’s αMPTI , which would then be positively associated with their α -diversity. To test the hypothesis, we calculated Shannon diversity and αMPTI for heterotrophic nanoflagellates (HNF; predator) and bacteria (prey) communities in the East China Sea (ECS). The HNF Shannon diversity was found to be positively associated with αMPTI of bacteria, which was then positively associated with bacterial Shannon diversity. In contrast, bacterial Shannon diversity did not correlate with HNF’s αMPTI . We argue that top-down control is one of the explanations to the positive α -diversity association among trophic levels in microbes of the ECS.

Fibroblast Growth Factor 9 Stimulates Neuronal Length Through NF-kB Signaling in Striatal Cell Huntington’s Disease Models - Issa Olakunle Yusuf; Hsiu-Mei Chen; Pei-Hsun Cheng; Chih-Yi Chang; Shaw-Jenq Tsai; Jih-Ing Chuang; Chia-Ching Wu; Bu-Miin Huang; H. Sunny Sun; Chuan-Mu Chen; Shang-Hsun Yang (Molecular Neurobiology, 2021)

Unexpected meteotsunamis prior to Typhoon Wipha and Typhoon Neoguri - Li-Ching Lin; Chin H. Wu (Natural Hazards, 2021)

Polycyclic aromatic hydrocarbon metabolites and mortality risk in an adult population - Yuan-Yuei Chen; Tung-Wei Kao; Chung-Ching Wang; Ying-Jen Chen; Chen-Jung Wu; Ching-Huang Lai; Wei-Liang Chen (Environmental Geochemistry and Health, 2021)

Detection and phylogenetic analysis of porcine circovirus type 3 in Taiwan - Chia-Chun Chang; Ching-Wei Wu; Yu-Chih Chang; Ching-Ying Wu; Maw-Sheng Chien; Chienjin Huang (Archives of Virology, 2021)

Doxorubicin metabolism moderately attributes to putative toxicity in prodigiosin/doxorubicin synergism in vitro cells - Shian-Ren Lin; Chun-Shu Lin; Ching-Cheng Chen; Feng-Jen Tseng; Tsung-Jui Wu; Lebin Weng; Ching-Feng Weng (Molecular and Cellular Biochemistry, 2020)
Doxorubicin (Dox) is a widely neoplasm chemotherapeutic drug with high incidences of cardiotoxicity. Prodigiosin (PG), a red bacterial pigment from Serratia marcescens , has been demonstrated to potentiate Dox’s cytotoxicity against oral squamous cell carcinoma cells through elevating Dox influx and identified as a Dox enhancer via PG-induced autophagy; however, toxicity of normal cell remains unclear. This study is conducted to evaluate putative cytotoxicity features of PG/Dox synergism in the liver, kidney, and heart cells and further elucidate whether PG augmented Dox’s effect via modulating Dox metabolism in normal cells. Murine hepatocytes FL83B, cardio-myoblast h9c2, and human kidney epithelial cells HK-2 were sequentially treated with PG and Dox by measuring cell viability, cell death characteristics, oxidative stress, Dox flux, and Dox metabolism. PG could slightly significant increase Dox cytotoxicity in all tested normal cells whose toxic alteration was less than that of oral squamous carcinoma cells. The augmentation of Dox cytotoxicity might be attributed to the increase of Dox-mediated ROS accumulation that might cause slight reduction of Dox influx and reduction of Dox metabolism. It was noteworthy to notice that sustained cytotoxicity appeared in normal cells after PG and Dox were removed. Taken together, moderately metabolic reduction of Dox might be ascribed to the mechanism of increase Dox cytotoxicity in PG-induced normal cells; nevertheless, the determination of PG/Dox dose with sustained cytotoxicity in normal cells needs to be comprehensively considered.

Two new diprenylated flavanones from Derris laxiflora Benth - Hui-Chi Huang; Shih-Chang Chien; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Hsi-Lin Chiu; Yueh-Hsiung Kuo (Natural Product Research, 2020)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

Heat-shock-induced tyrosinase gene ablation with CRISPR in zebrafish - Yu-Ching Wu; I-Jong Wang (Molecular Genetics and Genomics, 2020)

Establishing the ecological planning principles from empirical studies in agricultural environments of Taiwan - Chia-Ching Wu; Chun-Yen Chang (Landscape and Ecological Engineering, 2020)

Characterization of the monoclonal antibody specific to the ORF72 protein of koi herpesvirus and cellular distribution analysis of the viral protein - Ching‐Wei Wu; Ting‐Yun Wu; Chih‐Jung Kuo; Yi‐Ping Lu; Maw‐Sheng Chien; Chienjin Huang (Journal of Fish Diseases, 2020)
Koi herpesvirus (KHV) is an emerging pathogen of koi and common carp that causes a severe disease and mass mortality of infected fish. The KHV ORF72 protein is an important capsid protein that has been suggested to be a candidate for the development of diagnostic reagents and KHV vaccines. The purpose of this study was to clone and express the KHV ORF72 gene for further preparation of a specific monoclonal antibody (mAb) and to analyse cellular distribution of the viral protein. The mAb 3E1 could specifically recognize the expressed ORF72 protein of transfected cells by indirect immunofluorescence, and the antigenic site recognized by the mAb 3E1 was mapped to the region of N‐terminal 124 residues of KHV ORF72. This mAb was further demonstrated to specifically detect the KHV‐infected fish tissue by immunohistochemistry, thereby suggesting its high diagnostic potential. In addition, the cellular distribution analysis of the KHV ORF72 protein revealed that the region of amino acid residues 125–247 was related to mitochondrial localization and proliferation. Furthermore, a putative nuclear export signal (NES) of ORF72 at the residues 201–212 was confirmed on the basis of its function associated with NES activity.

Short-Term Variability of Biological Production and CO2 System Around Dongsha Atoll of the Northern South China Sea: Impact of Topography-Flow Interaction - Jen-Hua Tai; Wen-Chen Chou; Chin-Chang Hung; Kuan-Chieh Wu; Ying-Hsuan Chen; Tzong-Yueh Chen; Gwo-Ching Gong; Fuh-Kwo Shiah; Chun Hoe Chow (Frontiers in Marine Science, 2020)

Statistical Analysis on Heart Rate Variability for Graded Cardiopulmonary Groups with Different Exercise Intensities - Ching-Kun Chen; Shyan-Lung Lin; Cheng-Yi Huang; Tasi-Chu Wang; Ting-Yen Yao; Chieh-Liang Wu (Journal of Medical and Biological Engineering, 2020)

Genetic sequence changes related to the attenuation of avian infectious bronchitis virus strain TW2575/98 - Cheng-Ta Tsai; Hung-Yi Wu; Ching-Ho Wang (Virus Genes, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

The relationship between lead and cadmium levels and functional dependence among elderly participants - Yuan-Yuei Chen; Chung-Ching Wang; Tung-Wei Kao; Chen-Jung Wu; Ying-Jen Chen; Ching-Huang Lai; Yi-Chao Zhou; Wei-Liang Chen (Environmental Science and Pollution Research, 2020)

Urinary biomarkers of polycyclic aromatic hydrocarbons and the association with hearing threshold shifts in the United States adults - Cheng-Wai Chou; Yuan-Yuei Chen; Chung-Ching Wang; Tung-Wei Kao; Chen-Jung Wu; Ying-Jen Chen; Yi-Chao Zhou; Wei-Liang Chen (Environmental Science and Pollution Research, 2020)

An integrative assessment to determine the sediment toxicity of Kaohsiung Harbor in Taiwan: combining chemical analysis and cytotoxicity assay - Yun-Ru Ju; Chih-Feng Chen; Chiu-Wen Chen; Mei-Ling Tsai; Jia-Ching Wu; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Movement behaviour of released wild and farm-raised dolphinfish Coryphaena hippurus tracked by pop-up satellite archival tags - Shian-Jhong Lin; Michael K. Musyl; Sheng-Ping Wang; Nan-Jay Su; Wei-Chuan Chiang; Ching-Ping Lu; Kazuki Tone; Chang-Ying Wu; Akira Sasaki; Itsumi Nakamura; Kazuyoshi Komeyama; Ryo Kawabe (Fisheries Science, 2019)

Progressive multifocal leukoencephalopathy in a renal transplant patient - Tsu-Chen Lin; Mei-Yi Wu; Hui-Tzung Luh; Shiou-Fu Lin; Chien-Min Lin; Ying-Chi Tseng; Yung-Ching Liu; Mai-Szu Wu (Journal of NeuroVirology, 2019)

Exposure to polycyclic aromatic hydrocarbons and risk of disability among an elderly population - Yuan-Yuei Chen; Tung-Wei Kao; Chung-Ching Wang; Ying-Jen Chen; Chen-Jung Wu; Ching-Huang Lai; Wei-Liang Chen (Environmental Science and Pollution Research, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Hypoxia-Preconditioned Human Umbilical Vein Endothelial Cells Protect Against Neurovascular Damage After Hypoxic Ischemia in Neonatal Brain - Yi-Chao Lee; Ying-Chao Chang; Chia-Ching Wu; Chao-Ching Huang (Molecular Neurobiology, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Protein-bounded uremic toxin p-cresylsulfate induces vascular permeability alternations - Wei-Hua Tang; Chao-Ping Wang; Teng-Hung Yu; Pei-Yang Tai; Shih-Shin Liang; Wei-Chin Hung; Cheng-Ching Wu; Sung-Hao Huang; Yau-Jiunn Lee; Shih-Chieh Chen (Histochemistry and Cell Biology, 2018)

Effect of ventilation rate on air cleanliness and energy consumption in operation rooms at rest - Shih-Tseng Lee; Ching-Chieh Liang; Tsung-Yi Chien; Feng-Jen Wu; Kuang-Chung Fan; Gwo-Hwa Wan (Environmental Monitoring and Assessment, 2018)

Broad-specificity amino acid racemase, a novel non-antibiotic selectable marker for transgenic plants - Yi-Chia Kuan; Venkatesan Thiruvengadam; Jia-Shin Lin; Jia-Hsin Liu; Tsan-Jan Chen; Hsin-Mao Wu; Wen-Ching Wang; Liang-Jwu Chen (Plant Biotechnology Reports, 2018)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Anti-oxidative Responses on Hepatic Tissue of Zebrafish (Danio rerio) in a Short Duration of Sub-lethal Concentrations of Cadmium Exposure - Su Mei Wu; Li-Hsin Shu; Jia-Hao Liu; Ching Hsein Chen (Bulletin of Environmental Contamination and Toxicology, 2017)

Development of a TaqMan probe-based insulated isothermal PCR (TiiPCR) for the detection of Acidovorax citrulli, the bacterial pathogen of watermelon fruit blotch - Pei-Yi Wu; Lien-Chun Ho; Jun-Jie Chang; Kuo-Ching Tzeng; Wen-Ling Deng; Yi-Hsien Lin (European Journal of Plant Pathology, 2017)

Effect of adding brewery wastewater to pulp and paper mill effluent to enhance the photofermentation process: wastewater characteristics, biohydrogen production, overall performance, and kinetic modeling - Jacqueline Xiao Wen Hay; Ta Yeong Wu; Joon Ching Juan; Jamaliah Md. Jahim (Environmental Science and Pollution Research, 2017)

Optimization of Groundwater Quality Monitoring Network Using Risk Assessment and Geostatistic Approach - Shih -Ching Wu; Kai-Yuan Ke; Hsien-Tsung Lin; Yih-Chi Tan (Water Resources Management, 2017)

Infectious bursal disease virus as a replication-incompetent viral vector expressing green fluorescent protein - Yung-Yi C. Mosley; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2017)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

Indoxyl sulfate enhances IL-1β-induced E-selectin expression in endothelial cells in acute kidney injury by the ROS/MAPKs/NFκB/AP-1 pathway - Wen-Ching Shen; Chan-Jung Liang; Tao-Ming Huang; Chen-Wei Liu; Shu-Huei Wang; Guang-Huar Young; Jaw-Shiun Tsai; Ying-Chin Tseng; Yu-Sen Peng; Vin-Cent Wu; Yuh-Lien Chen (Archives of Toxicology, 2016)

Characterization of Rice Group 3 LEA Genes in Developmental Stages and Under Abiotic Stress - Yi-Ting Ke; Chung-An Lu; Shaw-Jye Wu; Ching-Hui Yeh (Plant Molecular Biology Reporter, 2016)

Inhibition of Peripheral TNF-α and Downregulation of Microglial Activation by Alpha-Lipoic Acid and Etanercept Protect Rat Brain Against Ischemic Stroke - Ming-Hsiu Wu; Chao-Ching Huang; Chung-Ching Chio; Kuen-Jer Tsai; Ching-Ping Chang; Nan-Kai Lin; Mao-Tsun Lin (Molecular Neurobiology, 2016)

A Smartphone Application Supporting Recovery from Heroin Addiction: Perspectives of Patients and Providers in China, Taiwan, and the USA - Marya Schulte; Di Liang; Fei Wu; Yu-Ching Lan; Wening Tsay; Jiang Du; Min Zhao; Xu Li; Yih -Ing Hser (Journal of Neuroimmune Pharmacology, 2016)

Anticancer activity of cryptotanshinone on acute lymphoblastic leukemia cells - Ching-Fen Wu; Sabine M. Klauck; Thomas Efferth (Archives of Toxicology, 2016)

Obesity Exacerbates Rat Cerebral Ischemic Injury through Enhancing Ischemic Adiponectin-Containing Neuronal Apoptosis - Ming-Hsiu Wu; Chung-Ching Chio; Kuen-Jer Tsai; Ching-Ping Chang; Nan-Kai Lin; Chao-Ching Huang; Mao-Tsun Lin (Molecular Neurobiology, 2016)

Chidamide alleviates TGF-β-induced epithelial–mesenchymal transition in lung cancer cell lines - Sheng-Hao Lin; Bing-Yen Wang; Ching-Hsiung Lin; Peng-Ju Chien; Yueh-Feng Wu; Jiunn-Liang Ko; Jeremy J. W. Chen (Molecular Biology Reports, 2016)

Rottlerin impairs the formation and maintenance of psychostimulant-supported memory - Tien You Liao; Wen-Yu Tzeng; Hsin-Hua Wu; Chianfang G. Cherng; Ching-Yi Wang; Sherry S-J. Hu; Lung Yu (Psychopharmacology, 2016)

Cardiac Fas-Dependent and Mitochondria-Dependent Apoptotic Pathways in a Transgenic Mouse Model of Huntington’s Disease - Bor-Tsang Wu; Ming-Chang Chiang; Ching-Yi Tasi; Chia-Hua Kuo; Woei-Cherng Shyu; Chung-Lan Kao; Chih-Yang Huang; Shin-Da Lee (Cardiovascular Toxicology, 2016)

Arsenic speciation in rice and risk assessment of inorganic arsenic in Taiwan population - Hsiu-Ling Chen; Ching-Chang Lee; Winn-Jung Huang; Han-Ting Huang; Yi-Chen Wu; Ya-Chen Hsu; Yi-Ting Kao (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Potential volume for CO2 deep ocean sequestration: an assessment of the area located on western Pacific Ocean - David Ching-Fang Shih; Yih-Min Wu; Jyr-Ching Hu (Stochastic Environmental Research and Risk Assessment, 2016)

Role of chicken melanoma differentiation-associated gene 5 in induction and activation of innate and adaptive immune responses to infectious bursal disease virus in cultured macrophages - Chih-Chun Lee; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2015)

Genotyping of turkey coronavirus field isolates from various geographic locations in the Unites States based on the spike gene - Yi-Ning Chen; Chien Chang Loa; Mustafa Mohammed-Khair Ababneh; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2015)

An indolylquinoline derivative promotes apoptosis in human lung cancer cells by impairing mitochondrial functions - Chun-Yen Liu; Pei-Tsen Wu; Jing-Ping Wang; Po-Wei Fan; Chang-Hung Hsieh; Chun-Li Su; Chien-Chih Chiu; Ching-Fa Yao; Kang Fang (Apoptosis, 2015)

A Numerical Study of Water Loss Rate Distributions in MDCT-Based Human Airway Models - Dan Wu; Shinjiro Miyawaki; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2015)

Cross‐talk between a regulatory small RNA , cyclic‐di‐ GMP signalling and flagellar regulator FlhDC for virulence and bacterial behaviours - Xiaochen Yuan; Devanshi Khokhani; Xiaogang Wu; Fenghuan Yang; Gabriel Biener; Benjamin J. Koestler; Valerica Raicu; Chenyang He; Christopher M. Waters; George W. Sundin; Fang Tian; Ching‐Hong Yang (Environmental Microbiology, 2015)
Summary D ickeya dadantii is a globally dispersed phytopathogen which causes diseases on a wide range of host plants. This pathogen utilizes the type III secretion system ( T3SS ) to suppress host defense responses, and secretes pectate lyase ( P el) to degrade the plant cell wall. Although the regulatory small RNA (s RNA ) RsmB , cyclic diguanylate monophosphate (c‐di‐ GMP ) and flagellar regulator have been reported to affect the regulation of these two virulence factors or multiple cell behaviours such as motility and biofilm formation, the linkage between these regulatory components that coordinate the cell behaviours remain unclear. Here, we revealed a sophisticated regulatory network that connects the s RNA , c‐di‐ GMP signalling and flagellar master regulator FlhDC . We propose multi‐tiered regulatory mechanisms that link the FlhDC to the T3SS through three distinct pathways including the FlhDC ‐ FliA ‐YcgR 3937 pathway; the FlhDC ‐ EcpC ‐ RpoN ‐ HrpL pathway; and the FlhDC ‐ rsmB ‐ RsmA ‐ HrpL pathway. Among these, EcpC is the most dominant factor for FlhDC to positively regulate T3SS expression.

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

Hydrolyzed 5-Azacytidine Enhances Differentiation of Rat Mesenchymal Stem Cells into Cardiomyocytes - Shwu Jen Chang; Yi-Jhen Wu; Shu Ching Tang; Hung-Yi Wang; Shyh Ming Kuo (Journal of Medical and Biological Engineering, 2015)

Identification and quantification of Cu-chlorophyll adulteration of edible oils - Mingchih Fang; Chia-Fen Tsai; Guan-Yan Wu; Su-Hsiang Tseng; Hwei-Fang Cheng; Ching-Hao Kuo; Che-Lun Hsu; Ya-Min Kao; Daniel Yang-Chih Shih; Yu-Mei Chiang (Food Additives & Contaminants Part B-Surveillance, 2015)

A single-repeat MYB transcription repressor, MYBH, participates in regulation of leaf senescence in Arabidopsis - Chun-Kai Huang; Pei-Ching Lo; Li-Fen Huang; Shaw-Jye Wu; Ching-Hui Yeh; Chung-An Lu (Plant Molecular Biology, 2015)

The eucalyptus oil ingredient 1,8-cineol induces oxidative DNA damage - Bastian Dörsam; Ching-Fen Wu; Thomas Efferth; Bernd Kaina; Jörg Fahrer (Archives of Toxicology, 2015)

Gene knockout of glutathione reductase 3 results in increased sensitivity to salt stress in rice - Tsung-Meng Wu; Wan-Rong Lin; Ching Huei Kao; Chwan-Yang Hong (Plant Molecular Biology, 2015)

CD200 in growing rat lungs: developmental expression and control by dexamethasone - Mang-Hung Tsai; Chin-Chen Chu; Tsui-Shan Wei; Mei-Miao Chiu; Chiu-Yun Chang; I-Hua Wei; Hsiung-Fei Chien; Hui-Min Chen; Ching-Hsiang Wu; Ya-Fen Jiang-Shieh (Cell and Tissue Research, 2015)

The expression of nitrate transporter genes reveals different nitrogen statuses of dominant diatom groups in the southern E ast C hina S ea - Lee‐Kuo Kang; Gwo‐Ching Gong; Yi‐Hsuan Wu; Jeng Chang (Molecular Ecology, 2015)
In this study, the m RNA levels of the Nrt2 nitrate transporter gene were used as a molecular indicator of nitrogen status in two dominant diatom groups, Skeletonema and Chaetoceros , which inhabit the southern East China Sea ( ECS ). To accurately interpret the abundance of Nrt2 transcripts in situ , maximum and minimum expression levels were determined under conditions of nitrogen deprivation and ammonium addition, respectively. In August 2010, Nrt2 transcript levels in Skeletonema at the inner shelf region exhibited a mean of 111 mmole/(mole EFL ); at the mid‐shelf region, the mean Nrt2 m RNA levels were 298 mmole/(mole EFL ), which was very close to the maximum levels observed under nitrogen starvation. By contrast, the Nrt2 transcript levels in Chaetoceros were low at all of the shelf locations, except at one station in the mid‐shelf region. The cross‐shelf mean was 2.86 mmole/(mole EFL ), which was similar to the expression levels observed in cultured Chaetoceros under conditions of sufficient ammonium. Similar expression patterns were observed in diatoms in the southern ECS in June 2011, but the Nrt2 transcript levels in Skeletonema at the inner shelf region were reduced to a mean of 28.6 mmole/(mole EFL ). Regression analysis indicated that cell abundance and Nrt2 expression were closely related to the nutricline depth in the coastward half of the southern ECS for Skeletonema but not for Chaetoceros . These results indicate that the evaluated species differ in nitrogen status, which may reflect their evolutionary strategies to survive in a fluctuating marine environment.

Is abnormal non-high-density lipoprotein cholesterol a gender-specific predictor for metabolic syndrome in patients with schizophrenia taking second-generation antipsychotics? - Esther Ching-Lan Lin; Wen-Chuan Shao; Hsin-Ju Yang; Miaofen Yen; Sheng-Yu Lee; Pei-Chun Wu; Ru-Band Lu (Metabolic Brain Disease, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

TGF-β1 mediates the radiation response of prostate cancer - Chun-Te Wu; Ching-Chuan Hsieh; Tzu-Chen Yen; Wen-Cheng Chen; Miao-Fen Chen (Journal of Molecular Medicine, 2015)

Bursal transcriptome of chickens protected by DNA vaccination versus those challenged with infectious bursal disease virus - Chih-Chun Lee; Bong-Suk Kim; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2015)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Aerosolized bovine lactoferrin reduces lung injury and fibrosis in mice exposed to hyperoxia - Hsiao-Ling Chen; Chih-Ching Yen; Shih-Ming Wang; Tung-Chou Tsai; Zi-Lun Lai; Jheng-Yue Sun; Willei Lin; Wu-Huei Hsu; Chuan-Mu Chen (BioMetals, 2014)

A Numerical Study of Heat and Water Vapor Transfer in MDCT-Based Human Airway Models - Dan Wu; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2014)

Expression of a gene encoding a rice RING zinc-finger protein, OsRZFP34, enhances stomata opening - Kuo-Hsuan Hsu; Chia-Chin Liu; Shaw-Jye Wu; Ying-Yu Kuo; Chung-An Lu; Ching-Rong Wu; Pei-Jyun Lian; Chwan-Yang Hong; Yi-Ting Ke; Juin-Hua Huang; Ching-Hui Yeh (Plant Molecular Biology, 2014)

An influenza A virus hemagglutinin (HA) epitope inserted in and expressed from several loci of the infectious bursal disease virus genome induces HA-specific antibodies - Yung-Yi C. Mosley; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2014)

Divergence of the expression and subcellular localization of CCR4-associated factor 1 (CAF1) deadenylase proteins in Oryza sativa - Wei-Lun Chou; Li-Fen Huang; Jhen-Cheng Fang; Ching-Hui Yeh; Chwan-Yang Hong; Shaw-Jye Wu; Chung-An Lu (Plant Molecular Biology, 2014)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

Chicken melanoma differentiation-associated gene 5 (MDA5) recognizes infectious bursal disease virus infection and triggers MDA5-related innate immunity - Chih-Chun Lee; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2014)

Optimal fallow area and location for multifunctional benefits of a paddy field during drought periods - Ching-Wen Chen; Nien-Sheng Hsu; Chieh-Shu Wu (Paddy and Water Environment, 2014)

Arsenic trioxide induces unfolded protein response in vascular endothelial cells - Ching-Yi Weng; Shu-Yuan Chiou; Lisu Wang; Mei-Chun Kou; Ying-Jan Wang; Ming-Jiuan Wu (Archives of Toxicology, 2014)

Determination of homogeneous regions for regional reference evapotranspiration estimation using the self-organizing map in western Taiwan - Ching-Tien Chen; Yu-Chuan Chang; Guan-Ting Wu (Paddy and Water Environment, 2014)

Differential gene expression in human hepatocyte cell lines exposed to the antiretroviral agent zidovudine - Jia-Long Fang; Tao Han; Qiangen Wu; Frederick A. Beland; Ching-Wei Chang; Lei Guo; James C. Fuscoe (Archives of Toxicology, 2013)

Identification and characterization of a novel chloroplast/mitochondria co-localized glutathione reductase 3 involved in salt stress response in rice - Tsung-Meng Wu; Wan-Rong Lin; Yun-Ting Kao; Yi-Ting Hsu; Ching-Hui Yeh; Chwan-Yang Hong; Ching Huei Kao (Plant Molecular Biology, 2013)

Histone deacetylase inhibitor AR-42 enhances E7-specific CD8+ T cell-mediated antitumor immunity induced by therapeutic HPV DNA vaccination - Sung Yong Lee; Zhuomin Huang; Tae Heung Kang; Ruey-Shyang Soong; Jayne Knoff; Ellen Axenfeld; Chenguang Wang; Ronald D. Alvarez; Ching-Shih Chen; Chien-Fu Hung; T.-C. Wu (Journal of Molecular Medicine, 2013)

Estimating Pumping Rates and Identifying Potential Recharge Zones for Groundwater Management in Multi-Aquifers System - Hsien-Tsung Lin; Kai-Yuan Ke; Yih-Chi Tan; Shih-Ching Wu; Gao Hsu; Po-Chia Chen; Shi-Ting Fang (Water Resources Management, 2013)

The integration of nautical hazard assessment and harbor GIS models to the Taichung Port area in Taiwan - Cheng-Wu Chen; Ching-Chung Lee; Chia-Hung Chen; Chun-Pin Tseng (Natural Hazards, 2013)

Toxicokinetics of tilapia following high exposure to waterborne and dietary copper and implications for coping mechanisms - Jeng-Wei Tsai; Yun-Ru Ju; Ying-Hsuan Huang; Yue-Sun Deng; Wei-Yu Chen; Chin-Ching Wu; Chung-Min Liao (Environmental Science and Pollution Research, 2013)

Erratum to: Significance of IL-6 in the transition of hormone-resistant prostate cancer and the induction of myeloid-derived suppressor cells - Chun-Te Wu; Ching-Chuan Hsieh; Cheng-Chia Lin; Wen-Cheng Chen; Ji-Hong Hong; Miao-Fen Chen (Journal of Molecular Medicine, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

A study of the frequency of methylation of gene promoter regions in colorectal cancer in the Taiwanese population - CHANG-CHIEH WU; JEN-CHUN KUAN; CHIH-HSIUNG HSU; TZU-AN CHEN; CHIEN-AN SUN; TSAN YANG; SHINN-LONG LIN; YU-CHING CHOU (Journal of Genetics, 2013)

Application of GIS for the determination of hazard hotspots after direct transportation linkages between Taiwan and China - Cheng-Wu Chen; Ching-Chung Lee; Chun-Pin Tseng; Chia-Hung Chen (Natural Hazards, 2013)

The switch of secondary sex determination in protandrous black porgy, Acanthopagrus schlegeli - Guan-Chung Wu; Ching-Fong Chang (Fish Physiology and Biochemistry, 2013)

A review of the anticancer and immunomodulatory effects of Lycium barbarum fruit - Wai-Man Tang; Enoch Chan; Ching-Yee Kwok; Yee-Ki Lee; Jian-Hong Wu; Chun-Wai Wan; Robbie Yat-Kan Chan; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2012)

Significance of IL-6 in the transition of hormone-resistant prostate cancer and the induction of myeloid-derived suppressor cells - Chun-Te Wu; Ching-Chuan Hsieh; Cheng-Chia Lin; Wen-Cheng Chen; Ji-Hong Hong; Miao-Fen Chen (Journal of Molecular Medicine, 2012)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

GIS-based evaluation on the fault motion-induced coseismic landslides - Ming-Wey Huang; Chien-Yuan Chen; Tzu-Hsiu Wu; Chi-Ling Chang; Sheu-Yien Liu; Ching-Yun Kao (Journal of Mountain Science, 2012)

Anti-Neuropilin-1 (MNRP1685A): Unexpected Pharmacokinetic Differences Across Species, from Preclinical Models to Humans - Yan Xin; Shuang Bai; Lisa A. Damico-Beyer; Denise Jin; Wei-Ching Liang; Yan Wu; Frank-Peter Theil; Amita Joshi; Yanmei Lu; John Lowe; Mauricio Maia; Rainer K. Brachmann; et al. (Pharmaceutical Research, 2012)

Noncontact erection is enhanced by Ginkgo biloba treatment in rats: role of neuronal NOS in the paraventricular nucleus and sacral spinal cord - Kuei-Ying Yeh; Ching-Hsiang Wu; Yuan-Feen Tsai (Psychopharmacology, 2012)

Coexisting mutations/polymorphisms of the long QT syndrome genes in patients with repaired Tetralogy of Fallot are associated with the risks of life-threatening events - Shuenn-Nan Chiu; Mei-Hwan Wu; Ming-Jai Su; Jou-Kou Wang; Ming-Tai Lin; Chien-Chih Chang; Hui-Wen Hsu; Ching-Tsuen Shen; Olivier Thériault; Mohamed Chahine (Human Genetics, 2012)

Arsenic modulates heme oxygenase-1, interleukin-6, and vascular endothelial growth factor expression in endothelial cells: roles of ROS, NF-κB, and MAPK pathways - Lisu Wang; Mei-Chun Kou; Ching-Yi Weng; Ling-Wei Hu; Ying-Jan Wang; Ming-Jiuan Wu (Archives of Toxicology, 2012)

Simvastatin reduces VCAM-1 expression in human umbilical vein endothelial cells exposed to lipopolysaccharide - Johnson Chia-Shen Yang; Faye Huang; Chia-Jung Wu; Yi-Chun Chen; Tsu-Hsiang Lu; Ching-Hua Hsieh (Inflammation Research, 2012)

The inhibition by di(2-ethylhexyl)-phthalate of erg-mediated K+ current in pituitary tumor (GH3) cells - Sheng-Nan Wu; Wei-Hsin Yang; Chia-Chen Yeh; Hsien-Ching Huang (Archives of Toxicology, 2012)

Lack of association between the genetic variations in the C-reactive protein gene and the risk of psoriasis among the Taiwanese - Ya-Ching Chang; Wei-Ming Wu; Lung-An Hsu (Molecular Biology Reports, 2012)

Induction of primitive pigment cell differentiation by visible light (helium–neon laser): a photoacceptor-specific response not replicable by UVB irradiation - Cheng-Che E. Lan; Shi-Bei Wu; Ching-Shuang Wu; Yi-Chun Shen; Tzu-Ying Chiang; Yau-Huei Wei; Hsin-Su Yu (Journal of Molecular Medicine, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Rilmenidine improves hepatic steatosis through p38-dependent pathway to higher the expression of farnesoid X receptor - Po-Sheng Yang; Hung-Tsung Wu; Hsien-Hui Chung; Chun-Ta Chen; Chin-Wen Chi; Ching-Hua Yeh; Juei-Tang Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Investigations into the Correlation Properties of Membrane Electroporation-Induced Inward Currents: Prediction of Pore Formation - Sheng-Nan Wu; Chia-Chen Yeh; Pei-Yu Wu; Hsien-Ching Huang; Mei-Ling Tsai (Cell Biochemistry and Biophysics, 2012)

Internal Exposure to Trace Elements in Non-smoking Residents Living in a Northern Taiwan Industrial City - Tser-Sheng Lin; Chin-Ching Wu (Biological Trace Element Research, 2011)

In vitro shoot induction and plant regeneration from flower buds in Paphiopedilum orchids - Yu-Ju Liao; Yu-Ching Tsai; Yung-Wei Sun; Ruey-Song Lin; Fang-Sheng Wu (In Vitro Cellular & Developmental Biology - Plant, 2011)

Infectious bursal disease DNA vaccination conferring protection by delayed appearance and rapid clearance of invading viruses - Yung-Yi Chen; Ming Kun Hsieh; Chun-Yu Tung; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2011)

An integrated flood risk assessment model for property insurance industry in Taiwan - Wen-Ko Hsu; Pei-Chiung Huang; Ching-Cheng Chang; Cheng-Wu Chen; Dung-Moung Hung; Wei-Ling Chiang (Natural Hazards, 2011)

Identification and characterization of a neutralizing-epitope-containing spike protein fragment in turkey coronavirus - Yi-Ning Chen; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2011)

Lactoferrin: an iron-binding antimicrobial protein against Escherichia coli infection - Chih-Ching Yen; Chih-Jie Shen; Wu-Huei Hsu; Yi-Hsin Chang; Hsin-Tang Lin; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2011)

Inorganic arsenic causes cell apoptosis in mouse cerebrum through an oxidative stress-regulated signaling pathway - Cheng Chien Yen; Tsung Jung Ho; Chin Ching Wu; Chun Fang Chang; Chin Chuan Su; Ya Wen Chen; Tzyy Rong Jinn; Tien Hui Lu; Po Wen Cheng; Yi Chang Su; Shing Hwa Liu; Chun Fa Huang (Archives of Toxicology, 2011)

Synthesis of Highly Selective Indole-Based Sensors for Mercuric Ion - Huei-Jyun Huang; Jiun-Ly Chir; Hsiu-Jung Cheng; Shau-Jiun Chen; Ching-Han Hu; An-Tai Wu (Journal of Fluorescence, 2011)

Data-oriented analyses of ciliate foraging behaviors - Yang-Chi Chang; Jang-Ching Yan; Jiang-Shiou Hwang; Cheng-Han Wu; Meng-Tsung Lee (Hydrobiologia, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Generation of transgenic watermelon resistant to Zucchini yellow mosaic virus and Papaya ringspot virus type W - Tsong-Ann Yu; Chu-Hui Chiang; Hui-Wen Wu; Chin-Mei Li; Ching-Fu Yang; Jun-Han Chen; Yu-Wen Chen; Shyi-Dong Yeh (Plant Cell Reports, 2011)

Differential distributions of CSE1L/CAS and E-cadherin in the polarized and non-polarized epithelial glands of neoplastic colorectal epithelium - Wu-Ching Uen; Cheng-Jeng Tai; Shing-Chuan Shen; Woan-Ruoh Lee; Tang-Yi Tsao; Win-Ping Deng; Hung-Yi Chiou; Chung-Huei Hsu; Cheng-I Hsieh; Ching-Fong Liao; Ming-Chung Jiang (Journal of Molecular Histology, 2010)

Role of DNA methyltransferase 1 in hormone-resistant prostate cancer - Miao-Fen Chen; Wen-Cheng Chen; Yu-Jia Chang; Ching-Fang Wu; Chun-Te Wu (Journal of Molecular Medicine, 2010)

Potential volume for CO2 deep ocean sequestration: an assessment of the area located on western Pacific Ocean - David Ching-Fang Shih; Yih-Min Wu; Jyr-Ching Hu (Stochastic Environmental Research and Risk Assessment, 2010)

5,5-Diphenyl-2-thiohydantoin-N10 (DPTH-N10) suppresses proliferation of cultured colon cancer cell line COLO-205 by inhibiting DNA synthesis and activating apoptosis - Tong-Sheng Lee; Li-Ching Chen; Yuan Liu; Jender Wu; Yu-Chih Liang; Wen-Sen Lee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Patterns of plant invasions in China: Taxonomic, biogeographic, climatic approaches and anthropogenic effects - Shan-Huah Wu; Hao-Ting Sun; Yung-Ching Teng; Marcel Rejmánek; Shu-Miaw Chaw; T.-Y. Aleck Yang; Chang-Fu Hsieh (Biological Invasions, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Diazoxide Reduces Status Epilepticus Neuron Damage in Diabetes - Chin-Wei Huang; Sheng-Nan Wu; Juei-Tang Cheng; Jing-Jane Tsai; Chao-Ching Huang (Neurotoxicity Research, 2010)

Lycopene binding compromised PDGF-AA/-AB signaling and migration in smooth muscle cells and fibroblasts: prediction of the possible lycopene binding site within PDGF - Ching-Pei Chen; Chi-Feng Hung; Shao-Chen Lee; Huey-Ming Lo; Pi-Hui Wu; Wen-Bin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Sea level fluctuations on the east coast of Taiwan that overlie continental shelf break - David Ching-Fang Shih; Yue-Gau Chen; Gwo-Fong Lin; Yih-Min Wu; Yee-Ping Jia; Chih-Ming Ma (Stochastic Environmental Research and Risk Assessment, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Health Risk of Consuming Heavy Metals in Farmed Tilapia in Central Taiwan - Min-Pei Ling; Hui-Tsung Hsu; Ruei-Hao Shie; Chin-Ching Wu; Yu-Syuan Hong (Bulletin of Environmental Contamination and Toxicology, 2009)

Uncertainty propagation of hydrodispersive transfer in an aquifer: an illustration of one-dimensional contaminant transport with slug injection - David Ching-Fang Shih; Yue-Gau Chen; Gwo-Fong Lin; Yih-Min Wu (Stochastic Environmental Research and Risk Assessment, 2009)

Serial cytokine levels in patients with severe sepsis - Huang-Pin Wu; Chian-Kuang Chen; Kong Chung; Jo-Chi Tseng; Chung-Ching Hua; Yu-Chih Liu; Duen-Yau Chuang; Chung-Han Yang (Inflammation Research, 2009)

In vitro effects of Helicobacter pylori-induced infection in gastric epithelial AGS cells on microglia-mediated toxicity in neuroblastoma SH-SY5Y cells - Yi-Ching Lo; Yu-Tzu Shih; Deng-Chyang Wu; Yi-Chern Lee (Inflammation Research, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Micro-Electrocardiograms to Study Post-Ventricular Amputation of Zebrafish Heart - Ping Sun; Yolanda Zhang; Fei Yu; Elizabeth Parks; Althea Lyman; Qiong Wu; Lisong Ai; Chang-Hong Hu; Qifa Zhou; Kirk Shung; Ching-Ling Lien; Tzung K. Hsiai (Annals of Biomedical Engineering, 2009)

Naringenin-Loaded Nanoparticles Improve the Physicochemical Properties and the Hepatoprotective Effects of Naringenin in Orally-Administered Rats with CCl4-Induced Acute Liver Failure - Feng-Lin Yen; Tzu-Hui Wu; Liang-Tzung Lin; Thau-Ming Cham; Chun-Ching Lin (Pharmaceutical Research, 2009)

Differential load impact upon arm tremor dynamics and coordinative strategy between postural holding and position tracking - Ing-Shiou Hwang; Yi-Ching Chen; Pei-Shan Wu (European Journal of Applied Physiology, 2009)

Diabetic Hyperglycemia Aggravates Seizures and Status Epilepticus-induced Hippocampal Damage - Chin-Wei Huang; Juei-Tang Cheng; Jing-Jane Tsai; Sheng-Nan Wu; Chao-Ching Huang (Neurotoxicity Research, 2009)

Development of a Methodology for Strategic Environmental Assessment: Application to the Assessment of Golf Course Installation Policy in Taiwan - Ching-Ho Chen; Ray-Shyan Wu; Wei-Lin Liu; Wen-Ray Su; Yu-Min Chang (Environmental Management, 2009)

Fruit Development, Ripening and Quality Related Genes in the Papaya Genome - Robert E. Paull; Beth Irikura; Pingfang Wu; Helen Turano; Nancy Jung Chen; Andrea Blas; John K. Fellman; Andrea R. Gschwend; Ching Man Wai; Qingyi Yu; Gernot Presting; Maqsudul Alam; et al. (Tropical Plant Biology, 2008)

Assessment of long-term variation in displacement for a GPS site adjacent to a transition zone between collision and subduction - David Ching-Fang Shih; Yih-Min Wu; Gwo-Fong Lin; Jyr-Ching Hu; Yue-Gau Chen; Chien-Hsin Chang (Stochastic Environmental Research and Risk Assessment, 2008)

Isolation and characterization of the zebrafish Danio rerio insulin-like growth factor binding protein-3 promoter region - Ming Jun CHOU; Jian Chyi CHEN; Jyh Yih CHEN; Hong Yi GONG; Li Tzu LI; Tzou Chi HUANG; Jen Leih WU; Ching Ming KUO (Fisheries Science, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

PaCDPK1, a gene encoding calcium-dependent protein kinase from orchid, Phalaenopsis amabilis, is induced by cold, wounding, and pathogen challenge - Tsung-Mu Tsai; Ying-Ru Chen; Tien-Wen Kao; Wen-Su Tsay; Chiou-Ping Wu; Ding-Ding Huang; Wen-Huei Chen; Ching-Chun Chang; Hao-Jen Huang (Plant Cell Reports, 2007)

Pulmonary actinomycosis: a case undergoing resection through video-assisted thoracic surgery (VATS) - Ming-shian Lin; Wea-lung Lin; Shi-ping Luh; Thomas Chang-yao Tsao; Tzu-ching Wu (Journal of Zhejiang University-SCIENCE B, 2007)

Evaluation of marine outfall with three-dimensional hydrodynamic and water quality modeling - Wen-Cheng Liu; Jan-Tai Kuo; Chih-Chieh Young; Ming-Ching Wu (Environmental Modeling & Assessment, 2007)

Application of statistical method in pollution episode analyses - Kuang-Jung Hsu; Ching-Chi Wu (Journal of Atmospheric Chemistry, 2007)

The Heilongjiang Group: A Jurassic accretionary complex in the Jiamusi Massif at the western Pacific margin of northeastern China - Fu‐Yuan Wu; Jin‐Hui Yang; Ching‐Hua Lo; Simon A. Wilde; De‐You Sun; Bor‐Ming Jahn (Island Arc, 2007)
The tectonic setting of the Eastern Asian continental margin in the Jurassic is highly controversial. In the current study, we have selected the Heilongjiang complex located at the western margin of the Jiamusi Massif in northeastern China for geochronological investigation to address this issue. Field and petrographic investigations indicate that the Heilongjiang complex is composed predominately of granitic gneiss, marble, mafic‐ultramafic rocks, blueschist, greenschist, quartzite, muscovite‐albite schist and two‐mica schist that were tectonically interleaved, indicating they represent a mélange. The marble, two‐mica schist and granitic gneiss were most probably derived from the Mashan complex, a high‐grade gneiss complex in the Jiamusi Massif with which the Heilongjiang Group is intimately associated. The ultramafic rocks, blueschist, greenschist and quartzite (chert) are similar to components in ophiolite. The sensitive high mass‐resolution ion microprobe U‐Pb zircon age of 265 ± 4 Ma for the granitic gneiss indicates that the protolith granite was emplaced coevally with Permian batholiths in the Jiamusi Massif. 40 Ar/ 39 Ar dating of biotite and phengite from the granitic gneiss and mica schist yields a late Early Jurassic metamorphic age between 184 and 174 Ma. Early components of the Jiamusi Massif, including the Mashan complex, probably formed part of an exotic block from Gondwana, affected by late Pan‐African orogenesis, and collided with the Asian continental margin during the Early Jurassic. Subduction of oceanic crust between the Jiamusi block and the eastern part of the Central Asian Orogenic Belt resulted in the formation of a huge volume of Jurassic granites in the Zhangguangcai Range. Consequently, the collision of the Jiamusi Massif with the Central Asian Orogenic Belt to the west can be considered as the result of circum‐Pacific accretion, unrelated to the Central Asian Orogenic Belt. The widespread development of Jurassic accretionary complexes along the Asian continental margin supports such an interpretation.

A web-based decision support system for slopeland hazard warning - Yu Fan-Chieh; Chen Chien-Yuan; Lin Sheng-Chi; Lin Yu-Ching; Wu Shang-Yu; Cheung Kei-Wai (Environmental Monitoring and Assessment, 2007)

Vertical ozone distributions observed using tethered ozonesondes in a coastal industrial city, Kaohsiung, in southern Taiwan - Ching-Ho Lin; Chin-Hsing Lai; Yee-Lin Wu; Hsin-Chih Lai; Po-Hsiung Lin (Environmental Monitoring and Assessment, 2007)

Induction of G2/M phase arrest and apoptosis by a novel enediyne derivative, THDA, in chronic myeloid leukemia (K562) cells - Zchong-Zcho Wu; Ching-Ming Chien; Sheng-Huei Yang; Yi-Hsiung Lin; Xiu-Wei Hu; Yu-Jhang Lu; Ming-Jung Wu; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2006)

Aluminum-inhibited root growth of rice seedlings is mediated through putrescine accumulation - Jen-Wu Wang; Ching Huei Kao (Plant and Soil, 2006)

Mutation in a homolog of yeast Vps53p accounts for the heat and osmotic hypersensitive phenotypes in Arabidopsis hit1-1 mutant - Chai-Fong Lee; Hsin-Yi Pu; Lian-Chin Wang; Ronald J. Sayler; Ching-Hui Yeh; Shaw-Jye Wu (Planta, 2006)

Mutation in a homolog of yeast Vps53p accounts for the heat and osmotic hypersensitive phenotypes in Arabidopsis hit1-1 mutant - Chai-Fong Lee; Hsin-Yi Pu; Lian-Chin Wang; Ronald J. Sayler; Ching-Hui Yeh; Shaw-Jye Wu (Planta, 2006)

Streptococcal pyrogenic exotoxin B causes mitochondria damage to polymorphonuclear cells preventing phagocytosis of Group A streptococcus - Chuan Chiang-Ni; Chih-Hung Wang; Pei-Jane Tsai; Woei-Jer Chuang; Yee-Shin Lin; Ming-T. Lin; Ching-Chuan Liu; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2006)

Contrasting phylogeographical patterns of two closely related species, Machilus thunbergii and Machilus kusanoi (Lauraceae), in Taiwan - Su‐Hwa Wu; Ching‐Yuan Hwang; Tsan‐Piao Lin; Jeng‐Der Chung; Yu‐Pin Cheng; Shih‐Ying Hwang (Journal of Biogeography, 2006)
Aim The purpose of this paper was to study the patterns of genetic variation, demographic history, haplotype relationships and potential location of diversity centres of two closely related species, Machilus thunbergii and Machilus kusanoi . Location The phylogeography of M. thunbergii and M. kusanoi was examined by sampling 110 and 106 individuals from 25 and 16 sampling sites, respectively, across their distributional range in Taiwan. Machilus thunbergii is distributed on the Asian mainland, South Korea, southern Japan, the Ryukyus, Taiwan and the Philippines, whereas M. kusanoi is endemic to Taiwan. These two species are closely related, and both are widely distributed in Taiwan but occupy different altitudinal zones and habitats. Methods The range‐wide variation of M. thunbergii and M. kusanoi in Taiwan was studied using chloroplast DNA (cpDNA) variations. A haplotype network was constructed with the computer program tcs . Nested clade analysis was conducted with the computer program ceodis , and various parameters of genetic diversity were calculated and neutrality tested by the computer program D na SP. Population differentiation was estimated using the programs arlequin and hapstep . The contribution of the populations to gene diversity and to allelic richness was calculated using the software contrib . The level of divergence for each population from the remaining populations was calculated as the mean value of pairwise F ST for each population against the rest of the populations. Results Extremely low levels of genetic differentiation were found for both species. This result suggested that these two species probably survived in multiple relict refugia with different population sizes throughout the island during low‐temperature periods of the Pleistocene. In addition, nested clade analysis (NCA) of cpDNA haplotypes indicated that restricted gene flow with isolation‐by‐distance characterized the recolonization after the Pleistocene by Tashueshan and Shiouhluan populations of M. thunbergii in the north‐central area west of the Central Mountain Range (CMR). In contrast, NCA analysis indicated that a major diversity centre on the southern tip of the island (Kending population) and contiguous range expansion characterized the recolonization by M. kusanoi of northern areas along the east side of the CMR. The major diversity centres found for the two species examined were further supported by the results of the mean F ST for individual populations in comparison with other populations, and of the contribution of the divergence component to the total diversity. Main conclusions This research supports the multiple relict refugia hypothesis for both species investigated. Populations of M. thunbergii at Shiouhluan and Tashueshan in the north‐central area west of the CMR represent a diversity centre currently expanding its size. A diversity centre at the southern‐edge population of M. kusanoi , and a contiguous range expansion from Kending, were found. These results indicate that the M. thunbergii populations at Tashueshan and Shiouhluan and the M. kusanoi population at Kending, and even Soukar, are evolutionarily significant units for conservation programmes.

Site-specific phosphorylation of L-form starch phosphorylase by the protein kinase activity from sweet potato roots - Guang-Huar Young; Han-Min Chen; Chi-Tsai Lin; Kuang-Ching Tseng; Jiann-Shing Wu; Rong-Huay Juang (Planta, 2006)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Molecular cloning and gonadotropin-releasing hormone regulation of receptor activated for C protein kinase (RACK) in tilapia Oreochromis mossambicus - Shu Ling HSIEH; Yuan Hwa RUAN; Chun Hsin WU; Ching Ming KUO (Fisheries Science, 2005)

Corals have already evolved the vertebrate-type hormone system in the sexual reproduction - Wen-Hung Twan; Hua-Fang Wu; Jiang-Shiou Hwang; Yan-Horn Lee; Ching-Fong Chang (Fish Physiology and Biochemistry, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Polyacetylenes Function as Anti-Angiogenic Agents - Li-Wha Wu; Yi-Ming Chiang; Hsiao-Ching Chuang; Sheng-Yang Wang; Ga-Wen Yang; Ya-Huey Chen; Ling-Ya Lai; Lie-Fen Shyur (Pharmaceutical Research, 2004)

Lack of association of ?-aminolevulinic acid dehydratase genotype with cytogenetic damage in lead workers - Fang-Yang Wu; Pao-Wen Chang; Chin-Ching Wu; Jim-Shoung Lai; Hsien-Wen Kuo (International Archives of Occupational and Environmental Health, 2004)

Detection of cefotaxime-resistant CTX-M-3 in clinical isolates ofSerratia marcescens - Mei-Fen Tsou; Wen-Liang Yu; Siu Wan Hung; Chizh-Ju Chi; Chieh-Ju; Ssu Ching Chen; Lii-Tzu Wu (Folia Microbiologica, 2004)

A Method for Locating Influential Pollution Sources and Estimating Their Contributions - Ching-Ho Lin; Yee-Lin Wu; Ken-Hui Chang; Chin-Hsing Lai (Environmental Modeling & Assessment, 2004)

Enhanced activity and enantioselectivity of Candida rugosa lipase immobilized on macroporous adsorptive resins for ibuprofen resolution - Hongwei Yu; Jinchuan Wu; Chi Bun Ching (Biotechnology Letters, 2004)

3-D Shear Wave Velocity Structure of the Crust and Upper Mantle in South China Sea and its Surrounding Regions by Surface Wave Dispersion Analysis - Hsin-Hung Wu; Yi-Ben Tsai; Tung-Yi Lee; Ching-Hua Lo; Chao-Hui Hsieh; Dinh Van Toan (Marine Geophysical Research, 2004)

Induction of Cell Death by Saponin and Antigen Delivery - Ching-An Wu; Ya-Wun Yang (Pharmaceutical Research, 2004)

Establishment of the mimetic aging effect in mice caused by D-galactose - Shih-Ching Ho; Jue-Hao Liu; ReY-Yih Wu (Biogerontology, 2003)

Relationship between blood lead levels and renal function in lead battery workers - Ven-Shing Wang; Ming-Tsung Lee; Jyh-Yann Chiou; Chiam-Fang Guu; Chin-Ching Wu; Trong-Neng Wu; Jim-Shoung Lai (International Archives of Occupational and Environmental Health, 2002)

Blood lead levels of primary-school children in Penghu County, Taiwan: distribution and influencing factors - Tsan Yang; Trong-Neng Wu; Shang-Wei Hsu; Ching-Huang Lai; Kquei-Nu Ko; Saou-Hsing Liou (International Archives of Occupational and Environmental Health, 2002)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)

Neurogenesis of cuneothalamic neurons and NO-containing neurons in the cuneate nucleus of the rat - Tsyr-Jiuan Wang; June-Horng Lue; Ching-Hsiang Wu; Jeng-Yung Shieh; Chen-Yuan Wen (Experimental Brain Research, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Distinct regulation of genes by bFGF and VEGF-A in endothelial cells - Yng-Jyh Jih; Wen-Hui Lien; Wen-Chi Tsai; Ga-Wen Yang; Ching Li; Li-Wha Wu (Angiogenesis, 2001)